Conductive particles, conductive materials and connection structures

JP7636894B2Active Publication Date: 2025-02-27SEKISUI CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020538861
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-19
Filing Date
2020-03-19
Publication Date
2025-02-27
Estimated Expiration
2040-03-19

AI Technical Summary

Benefits of technology

【0031】 本発明に係る導電性粒子は、基材粒子と、上記基材粒子の表面上に配置された第1の導電部と、上記第1の導電部の表面上に配置された第2の導電部とを備える。本発明に係る導電性粒子では、上記第1の導電部が、ニッケルとホウ素とを含み、かつ、リンを含まない。本発明に係る導電性粒子では、上記第1の導電部の内表面から外側に向かって厚み1/5の領域の100重量%中におけるホウ素の平均含有量と、上記第1の導電部の外表面から内側に向かって厚み1/5の領域の100重量%中におけるホウ素の平均含有量との差の絶対値が、0重量%以上10重量%以下である。本発明に係る導電性粒子では、上記第1の導電部における主金属の標準電極電位が、上記第2の導電部における主金属の標準電極電位よりも小さい。本発明に係る導電性粒子では、上記の構成が備えられているので、実装時に導電部の割れの発生を効果的に抑制することができ、電極間の接続抵抗を効果的に低くすることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636894000005
    Figure 0007636894000005
  • Figure 0007636894000006
    Figure 0007636894000006
  • Figure 0007636894000007
    Figure 0007636894000007
Patent Text Reader

Abstract

Provided is a conductive particle which makes it possible to effectively suppress cracking of a conductive portion during mounting and effectively reduce connection resistance between electrodes. The conductive particle according to the present invention includes a base particle, a first conductive portion arranged on the surface of the base particle, and a second conductive portion arranged on the surface of the first conductive portion, the first conductive portion includes nickel and boron and does not contain phosphorus, an absolute value of the difference between an average amount of boron in 100% by weight in a region having a thickness of 1 / 5 from the inner surface of the first conductive portion toward the outer side and an average amount of boron in 100% by weight in a region having a thickness of 1 / 5 from the outer surface of the first conductive portion toward the inner side is 0-10% by weight, and a standard electrode potential of a main metal in the first conductive portion is smaller than a standard electrode potential of a main metal in the second conductive portion.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive particle having a conductive portion disposed on the surface of a base particle. The present invention also relates to a conductive material and a connection structure using the conductive particle. [Background technology]

[0002] Anisotropic conductive materials, such as anisotropic conductive pastes and anisotropic conductive films, are widely known, in which conductive particles are dispersed in a binder resin.

[0003] The anisotropic conductive material is used to obtain various connection structures. Examples of connections using the anisotropic conductive material include connections between a flexible printed circuit board and a glass substrate (FOG (Film on Glass)), between a semiconductor chip and a flexible printed circuit board (COF (Chip on Film)), between a semiconductor chip and a glass substrate (COG (Chip on Glass)), and between a flexible printed circuit board and a glass epoxy substrate (FOB (Film on Board)).

[0004] When the anisotropic conductive material is used to electrically connect, for example, an electrode of a semiconductor chip and an electrode of a glass substrate, an anisotropic conductive material containing conductive particles is placed on the glass substrate. Next, the semiconductor chips are stacked, and heated and pressurized. This causes the anisotropic conductive material to harden, electrically connecting the electrodes via the conductive particles to obtain a connection structure.

[0005] As an example of the conductive particle, the following Patent Document 1 discloses a conductive particle including a core particle, a Ni plating layer, a precious metal plating layer, and an anti-rust film. The Ni plating layer covers the core particle and contains Ni. The precious metal plating layer covers at least a part of the Ni plating layer and contains at least one of Au and Pd. The anti-rust film covers at least one of the plating layer and the precious metal plating layer and contains an organic compound. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-20721 A Summary of the Invention [Problem to be solved by the invention]

[0007] In recent years, when an anisotropic conductive material is used to obtain a connection structure, a connection at a lower pressure than before, i.e., a so-called low-pressure mounting, is being performed in the electrode connection process. For example, when a semiconductor chip is directly mounted on a flexible printed circuit board, it is necessary to perform mounting at a low pressure in order to suppress deformation of the flexible printed circuit board.

[0008] However, in mounting at low pressure, the pressure applied to the conductive particles in the anisotropic conductive material is low, and sufficient conductive reliability may not be obtained. For this reason, a precious metal with a low resistance value may be used on the outermost surface of the conductive part, and a precious metal part may be formed.

[0009] In addition, when there is a potential difference between the conductive part and the electrode, or when a protective layer is present to protect the surface of the electrode, the conductive part containing nickel may corrode and sufficient electrical reliability may not be obtained. For this reason, a precious metal may be used on the outermost surface of the conductive part to prevent corrosion, and a precious metal part may be formed.

[0010] When a precious metal portion is formed on the outermost surface of a conductive portion, metal diffusion may occur between the precious metal portion and the underlying metal portion (generally a nickel-phosphorus alloy), and an amorphous portion (phosphorus-rich portion) may be formed between the precious metal portion and the underlying metal portion. When an amorphous portion (phosphorus-rich layer) is formed between the precious metal portion and the underlying metal portion, cracks may occur in the conductive portion during mounting. As a result, it may be difficult to sufficiently increase the reliability of electrical continuity between the electrodes.

[0011] In addition, the nickel-phosphorus alloy used for the base metal may have a higher resistance value than nickel-boron alloy, pure nickel, etc. As a result, it may be difficult to sufficiently reduce the connection resistance between electrodes.

[0012] An object of the present invention is to provide a conductive particle that can effectively suppress the occurrence of cracks in a conductive part during mounting and can effectively reduce the connection resistance between electrodes. Another object of the present invention is to provide a conductive material and a connection structure using the conductive particle. [Means for solving the problem]

[0013] According to a broad aspect of the present invention, there is provided a conductive particle comprising a base particle, a first conductive portion disposed on a surface of the base particle, and a second conductive portion disposed on a surface of the first conductive portion, wherein the first conductive portion contains nickel and boron but does not contain phosphorus, the absolute value of the difference between the average boron content in 100 weight% of a region that is 1 / 5 of the thickness from the inner surface of the first conductive portion toward the outside and the average boron content in 100 weight% of a region that is 1 / 5 of the thickness from the outer surface of the first conductive portion toward the inside is between 0 weight% and 10 weight%, and the standard electrode potential of a main metal in the first conductive portion is smaller than the standard electrode potential of a main metal in the second conductive portion.

[0014] In a specific aspect of the conductive particle according to the present invention, the absolute value of the difference between the standard electrode potential of the main metal in the first conductive portion and the standard electrode potential of the main metal in the second conductive portion is 0.05V or more and 3V or less.

[0015] In a specific aspect of the conductive particle according to the present invention, the average boron content in 100 weight% of a region 1 / 5 of the thickness from the inner surface of the first conductive portion toward the outside is 0 weight% or more and 10 weight% or less, and the average boron content in 100 weight% of a region 1 / 5 of the thickness from the outer surface of the first conductive portion toward the inside is 0 weight% or more and 10 weight% or less.

[0016] In a specific aspect of the conductive particle according to the present invention, the first conductive portion has an average nickel content of 50% by weight or more and 99.9% by weight or less in 100% by weight of the entire portion.

[0017] In a specific aspect of the conductive particle according to the present invention, the first conductive portion has an average boron content of 0.001% by weight or more and 10% by weight or less in 100% by weight of the entire portion.

[0018] In a specific aspect of the conductive particle according to the present invention, a main metal in the second conductive portion is tin, copper, palladium, ruthenium, platinum, silver, rhodium, iridium, or gold.

[0019] In a specific aspect of the conductive particle according to the present invention, an outer surface of the second conductive portion is subjected to an anti-rust treatment.

[0020] In a specific aspect of the conductive particle according to the present invention, the outer surface of the second conductive portion is subjected to an anti-rust treatment with a compound having an alkyl group having 6 to 22 carbon atoms.

[0021] In a specific aspect of the conductive particle according to the present invention, the particle diameter of the base particle is 0.1 μm or more and 100 μm or less.

[0022] In a specific aspect of the conductive particle according to the present invention, the first conductive portion or the second conductive portion has a plurality of protrusions on an outer surface thereof.

[0023] In a particular aspect of the conductive particle according to the present invention, the first conductive portion or the second conductive portion has a plurality of core materials inside or on the inside thereof that raise the surface of the first conductive portion or the second conductive portion so as to form a plurality of the protrusions.

[0024] In a particular aspect of the conductive particle according to the present invention, the first conductive portion or the second conductive portion does not have a plurality of core materials inside or on the inside thereof that raise the surface of the first conductive portion or the second conductive portion so as to form a plurality of the protrusions.

[0025] In a specific aspect of the conductive particle according to the present invention, the conductive particle includes an insulating material disposed on an outer surface of the second conductive portion.

[0026] In a specific aspect of the conductive particles according to the present invention, the conductive particles are used for conductive connection of an electrode with a protective layer, the electrode comprising an electrode and a protective layer disposed on a surface of the electrode.

[0027] In a specific aspect of the conductive particles according to the present invention, the conductive particles are used for conductive connection of electrodes of a flexible member.

[0028] According to a broad aspect of the present invention, there is provided a conductive material including the above-described conductive particles and a binder resin.

[0029] According to a broad aspect of the present invention, there is provided a connection structure comprising a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection portion connecting the first connection target member and the second connection target member, wherein the connection portion is formed from the conductive particles described above or is formed from a conductive material containing the conductive particles and a binder resin, and the first electrode and the second electrode are electrically connected by the conductive particles.

[0030] In a specific aspect of the connection structure according to the present invention, a standard electrode potential of a base metal in the first conductive portion is lower than a standard electrode potential of a base metal on an outer surface of the first electrode or the second electrode. Effect of the Invention

[0031] The conductive particle according to the present invention includes a base particle, a first conductive part disposed on the surface of the base particle, and a second conductive part disposed on the surface of the first conductive part. In the conductive particle according to the present invention, the first conductive part contains nickel and boron, and does not contain phosphorus. In the conductive particle according to the present invention, the absolute value of the difference between the average content of boron in 100% by weight of a region having a thickness of 1 / 5 from the inner surface of the first conductive part toward the outside and the average content of boron in 100% by weight of a region having a thickness of 1 / 5 from the outer surface of the first conductive part toward the inside is 0% by weight or more and 10% by weight or less. In the conductive particle according to the present invention, the standard electrode potential of the main metal in the first conductive part is lower than the standard electrode potential of the main metal in the second conductive part. Since the conductive particle according to the present invention has the above configuration, it is possible to effectively suppress the occurrence of cracks in the conductive part during mounting, and to effectively reduce the connection resistance between electrodes. [Brief description of the drawings]

[0032] [Figure 1] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing a conductive particle according to a fourth embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic diagram illustrating each region for determining the average boron content in the first conductive portion of the conductive particle according to the first embodiment of the present invention. [Figure 6] FIG. 6 is a schematic diagram illustrating each region for determining the average boron content in a first conductive portion in a conductive particle according to a second embodiment of the present invention. [Figure 7] FIG. 7 is a front cross-sectional view that illustrates a connection structure using conductive particles according to the first embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] The present invention will be described in detail below.

[0034] (Conductive particles) The conductive particle according to the present invention includes a base particle, a first conductive portion disposed on a surface of the base particle, and a second conductive portion disposed on a surface of the first conductive portion. In the conductive particle according to the present invention, the first conductive portion contains nickel and boron, but does not contain phosphorus. In the conductive particle according to the present invention, the absolute value of the difference between the average boron content in 100% by weight of a region having a thickness of 1 / 5 from the inner surface of the first conductive portion toward the outside and the average boron content in 100% by weight of a region having a thickness of 1 / 5 from the outer surface of the first conductive portion toward the inside is 0% by weight or more and 10% by weight or less. In the conductive particle according to the present invention, the standard electrode potential of the main metal in the first conductive portion is smaller than the standard electrode potential of the main metal in the second conductive portion.

[0035] Since the conductive particles according to the present invention have the above-mentioned configuration, the occurrence of cracks in the conductive portion during mounting can be effectively suppressed, and the connection resistance between electrodes can be effectively reduced.

[0036] In general, when a conductive layer containing nickel and boron is formed by electroless plating, the boron content in the plating bath changes as the plating proceeds. Therefore, there is a difference in the absolute value of the difference between the average boron content in 100% by weight of the region having a thickness of 1 / 5 from the inner surface of the first conductive part toward the outside and the average boron content in 100% by weight of the region having a thickness of 1 / 5 from the outer surface of the first conductive part toward the inside. In the present invention, the temperature during the reaction, the nickel ion concentration, the reducing agent dropping rate, the stirring conditions, and the like are appropriately controlled, and a method is adopted to keep the boron content in the nickel plating film uniform with high accuracy when the nickel plating film is formed, thereby realizing a reduction in the absolute value.

[0037] In low-voltage mounting, in order to ensure sufficient conduction reliability and to prevent corrosion of the conductive parts, a precious metal may be used on the outermost surface of the conductive parts, forming a precious metal part.

[0038] When a precious metal portion is formed on the outermost surface of a conductive portion, metal diffusion may occur between the precious metal portion and the underlying metal portion (generally a nickel-phosphorus alloy), and an amorphous portion (phosphorus-rich portion) may be formed between the precious metal portion and the underlying metal portion. When an amorphous portion (phosphorus-rich portion) is formed between the precious metal portion and the underlying metal portion, cracks may occur in the conductive portion during mounting. As a result, it may be difficult to sufficiently increase the reliability of conduction between electrodes with conventional conductive particles.

[0039] In addition, the nickel-phosphorus alloy used for the base metal may have a higher resistance value than nickel-boron alloy, pure nickel, etc. As a result, it may be difficult to sufficiently reduce the connection resistance between electrodes.

[0040] Since the conductive particles according to the present invention have the above-mentioned configuration, even if a precious metal is used in the conductive portion, metal diffusion does not occur between the precious metal portion and the base metal portion, and an amorphous portion (phosphorus-rich portion) is not formed between the precious metal portion and the base metal portion. Therefore, the occurrence of cracks in the conductive portion during mounting can be effectively suppressed, and the connection resistance between the electrodes can be effectively reduced.

[0041] In the conductive particle according to the present invention, the standard electrode potential of the main metal in the first conductive part is smaller than the standard electrode potential of the main metal in the second conductive part. From the viewpoint of more effectively suppressing the occurrence of cracks in the conductive part during mounting and more effectively lowering the connection resistance between electrodes, the absolute value of the difference between the standard electrode potential of the main metal in the first conductive part and the standard electrode potential of the main metal in the second conductive part is preferably 0.05V or more, more preferably 0.1V or more, and even more preferably 0.5V or more. From the viewpoint of more effectively suppressing the occurrence of cracks in the conductive part during mounting and more effectively lowering the connection resistance between electrodes, the absolute value of the difference between the standard electrode potential of the main metal in the first conductive part and the standard electrode potential of the main metal in the second conductive part is preferably 3V or less, more preferably 2.1V or less, and even more preferably 1.3V or less. The main metal in the conductive part means the metal species that is contained most abundantly among the metal species contained in the conductive part.

[0042] The present invention will now be described in detail with reference to the drawings.

[0043] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention.

[0044] The conductive particle 1 shown in FIG. 1 includes a base particle 2, a first conductive portion 3, and a second conductive portion 4. The first conductive portion 3 is disposed on the surface of the base particle 2. The second conductive portion 4 is disposed on the surface of the first conductive portion 3. In the conductive particle 1, the first conductive portion 3 is disposed on the surface of the base particle 2, and the second conductive portion 4 is disposed on the surface of the first conductive portion 3. In this embodiment, the conductive particle 1 is a coated particle in which the surface of the base particle 2 is coated with the first conductive portion 3, and the surface of the first conductive portion 3 is coated with the second conductive portion 4. In the conductive particle, the entire surface of the base particle may be covered with the first conductive portion, or a part of the surface of the base particle may be covered with the first conductive portion. In the conductive particle, the entire surface of the first conductive portion may be covered with the second conductive portion, or a part of the surface of the first conductive portion may be covered with the second conductive portion.

[0045] In the conductive particle 1, the first conductive portion 3 contains nickel and boron, but does not contain phosphorus. The absolute value of the difference between the average boron content in 100% by weight of the region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive portion 3 toward the outside and the average boron content in 100% by weight of the region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive portion 3 toward the inside is 0% by weight or more and 10% by weight or less. When the absolute value is 0% by weight, the average boron content in the two regions (R1) and (R2) is the same. The region (R1) is the region between the inner surface of the first conductive portion 3 (the outer surface of the base particle 2) and the dashed line L1 in FIG. 5. The region (R2) is the region between the outer surface of the first conductive portion 3 (the inner surface of the second conductive portion 4) and the dashed line L2 in FIG. 5.

[0046] Unlike the conductive particle 21 described later, the conductive particle 1 does not have a core material. Unlike the conductive particles 21 and 31 described later, the conductive particle 1 does not have protrusions. The conductive particle 1 is spherical. The first conductive part 3 and the second conductive part 4 do not have protrusions on their outer surfaces. In this way, the conductive particle according to the present invention may not have protrusions on the conductive surface and may be spherical. Moreover, unlike the conductive particles 21 and 31 described later, the conductive particle 1 does not have an insulating material. However, the conductive particle 1 may have an insulating material arranged on the outer surface of the second conductive part 4.

[0047] In the conductive particle 1, the base particle 2 is in contact with the first conductive portion 3. In the conductive particle 1, the first conductive portion 3 is in contact with the second conductive portion 4.

[0048] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention.

[0049] The conductive particle 11 shown in FIG. 2 comprises a base particle 2, a first conductive portion 13, and a second conductive portion 4.

[0050] The conductive particle 1 and the conductive particle 11 have different first conductive parts 3 and 13. The first conductive part 13 has a conductive part 13A arranged on the base particle 2 side and a conductive part 13B arranged on the opposite side to the base particle 2 side. The conductive particle 1 has a first conductive part 3 having a single layer structure, whereas the conductive particle 11 has a first conductive part 13 having a two-layer structure including the conductive part 13A and the conductive part 13B. The conductive part 13A and the conductive part 13B may be formed as different conductive parts or may be formed as the same conductive layer. The first conductive part may have a single layer structure or a multi-layer structure of two or more layers.

[0051] The conductive portion 13A is disposed on the surface of the base particle 2. The conductive portion 13A is disposed between the base particle 2 and the conductive portion 13B. The conductive portion 13A is in contact with the base particle 2. The conductive portion 13B is in contact with the conductive portion 13A. The conductive portion 13A is disposed on the surface of the base particle 2, and the conductive portion 13B is disposed on the outer surface of the conductive portion 13A.

[0052] In the conductive particle 11, the first conductive portion 13 contains nickel and boron, but does not contain phosphorus. For example, the conductive portion 13A may be a nickel-boron plating layer, and the conductive portion 13B may be a pure nickel layer or a nickel-tin alloy layer. The absolute value of the difference between the average boron content in 100% by weight of a region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive portion 13 toward the outside and the average boron content in 100% by weight of a region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive portion 13 toward the inside is 0% by weight or more and 10% by weight or less. The above region (R1) is the region between the inner surface of the first conductive portion 13 (the inner surface of the conductive portion 13A, the outer surface of the base particle 2) and the dashed line L1 in FIG. 6. The region (R2) is the region between the outer surface of first conductive portion 13 (the outer surface of conductive portion 13B, the inner surface of second conductive portion 4) and dashed line L2 in Fig. 6. When the first conductive portion has a multi-layer structure of two or more layers, the regions (R1) and (R2) are preferably calculated from the thickness of the entire first conductive portion.

[0053] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention.

[0054] 3 includes a base particle 2, a first conductive portion 23, a second conductive portion 24, a plurality of core materials 25, and a plurality of insulating materials 26. The first conductive portion 23 is disposed on the surface of the base particle 2. The second conductive portion 24 is disposed on the surface of the first conductive portion 23. In the conductive particle 21, the first conductive portion 23 is disposed on the surface of the base particle 2, and the second conductive portion 24 is disposed on the surface of the first conductive portion 23.

[0055] In the conductive particle 21, the first conductive portion 23 contains nickel and boron, but does not contain phosphorus. The absolute value of the difference between the average boron content in 100 weight% of a region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive portion 23 toward the outside and the average boron content in 100 weight% of a region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive portion 3A toward the inside is 0 weight% or more and 10 weight% or less.

[0056] The conductive particle 21 has a plurality of protrusions 21A on its conductive surface. The first conductive portion 23 has a plurality of protrusions 23A on its outer surface. The second conductive portion 24 has a plurality of protrusions 24A on its outer surface. A plurality of core substances 25 are disposed on the surface of the base particle 2. The plurality of core substances 25 are embedded in the first conductive portion 23. The plurality of core substances 25 are embedded inside the second conductive portion 24. The core substances 25 are disposed inside the protrusions 21A, 23A, and 24A. The first conductive portion 23 covers the plurality of core substances 25. The outer surfaces of the first conductive portion 23 and the second conductive portion 24 are raised by the plurality of core substances 25, forming the protrusions 21A, 23A, and 24A.

[0057] The conductive particle 21 has an insulating material 26 arranged on the outer surface of the second conductive portion 24. At least a part of the outer surface of the second conductive portion 24 is covered with the insulating material 26. The insulating material 26 is formed of a material having insulating properties. In this embodiment, the insulating material 26 is an insulating particle. In this manner, the conductive particle according to the present invention may have the insulating material arranged on the outer surface of the second conductive portion. However, the conductive particle according to the present invention does not necessarily have to have the insulating material.

[0058] FIG. 4 is a cross-sectional view showing a conductive particle according to a fourth embodiment of the present invention.

[0059] 4 includes a base particle 2, a first conductive portion 33, a second conductive portion 34, and a plurality of insulating materials 26. The first conductive portion 33 is disposed on the surface of the base particle 2. The second conductive portion 34 is disposed on the surface of the first conductive portion 33. In the conductive particle 31, the first conductive portion 33 is disposed on the surface of the base particle 2, and the second conductive portion 34 is disposed on the surface of the first conductive portion 33.

[0060] In the conductive particle 31, the first conductive portion 33 contains nickel and boron, but does not contain phosphorus. The absolute value of the difference between the average boron content in 100 weight% of a region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive portion 33 toward the outside and the average boron content in 100 weight% of a region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive portion 3B toward the inside is 0 weight% or more and 10 weight% or less.

[0061] Unlike conductive particles 21, conductive particles 31 do not have a core material. Conductive particles 31 do not have a core material, but have a plurality of protrusions 31A on their conductive surface. First conductive portion 33 has a plurality of protrusions 33A on its outer surface. Second conductive portion 34 has a plurality of protrusions 34A on its outer surface.

[0062] The first conductive portion 33 has a first portion and a second portion that is thicker than the first portion. The portion excluding the multiple protrusions constitutes the first portion of the first conductive portion 33. The multiple protrusions constitute the second portion of the first conductive portion 33 that is thicker.

[0063] The conductive particle 31 has an insulating material 26 arranged on the outer surface of the second conductive portion 34. At least a part of the outer surface of the second conductive portion 34 is covered with the insulating material 26. The insulating material 26 is formed of a material having insulating properties. In this embodiment, the insulating material 26 is an insulating particle. In this manner, the conductive particle according to the present invention may have the insulating material arranged on the outer surface of the second conductive portion. However, the conductive particle according to the present invention does not necessarily have to have the insulating material.

[0064] Other details of the conductive particles will be described below.

[0065] (base material particles) The base particles include resin particles, inorganic particles other than metal particles, organic-inorganic hybrid particles, and metal particles. The base particles are preferably base particles other than metal particles, and more preferably resin particles, inorganic particles other than metal particles, or organic-inorganic hybrid particles. The base particles may have a core and a shell disposed on the surface of the core, and may be core-shell particles. The core may be an organic core, and the shell may be an inorganic shell.

[0066] The base particles are more preferably resin particles or organic-inorganic hybrid particles, and may be resin particles or organic-inorganic hybrid particles. When the conductive particles are used to connect electrodes, the conductive particles are placed between the electrodes and then compressed by pressure bonding. When the base particles are resin particles or organic-inorganic hybrid particles, the conductive particles are easily deformed during the pressure bonding, and the contact area between the conductive particles and the electrodes is increased. Therefore, the reliability of conduction between the electrodes can be further improved.

[0067] As the resin for forming the resin particles, various organic substances are suitably used. As the resin for forming the resin particles, for example, polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, polybutadiene, etc.; acrylic resins such as polymethyl methacrylate and polymethyl acrylate, etc.; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyether ether ketone, polyether sulfone, divinylbenzene polymer, and divinylbenzene copolymer. As the divinylbenzene copolymer, etc., divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylic acid ester copolymer, etc. can be mentioned. Since the hardness of the resin particles can be easily controlled within a suitable range, it is preferable that the resin for forming the resin particles is a polymer obtained by polymerizing one or more polymerizable monomers having an ethylenically unsaturated group.

[0068] When the resin particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, the polymerizable monomer having an ethylenically unsaturated group includes a non-crosslinkable monomer and a crosslinkable monomer.

[0069] Examples of the non-crosslinkable monomer include styrene-based monomers such as styrene and α-methylstyrene; carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride; alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, and the like. Examples of the monomers include oxygen-containing (meth)acrylate compounds such as acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; unsaturated hydrocarbons such as ethylene, propylene, isoprene, and butadiene; and halogen-containing monomers such as trifluoromethyl (meth)acrylate, pentafluoroethyl (meth)acrylate, vinyl chloride, vinyl fluoride, and chlorostyrene.

[0070] Examples of the crosslinkable monomer include tetramethylolmethane tetra(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly) Examples of suitable (meth)acrylates include polyfunctional (meth)acrylate compounds such as propylene glycol di(meth)acrylate, (poly)tetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; and silane-containing monomers such as triallyl (iso)cyanurate, triallyl trimellitate, divinylbenzene, diallyl phthalate, diallyl acrylamide, diallyl ether, γ-(meth)acryloxypropyltrimethoxysilane, trimethoxysilylstyrene, and vinyltrimethoxysilane.

[0071] The resin particles can be obtained by polymerizing the polymerizable monomer having an ethylenically unsaturated group by a known method, such as a method of suspension polymerization in the presence of a radical polymerization initiator, and a method of swelling and polymerizing a monomer together with a radical polymerization initiator using non-crosslinked seed particles.

[0072] The particle diameter of the resin particles is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 1.5 μm or more, particularly preferably 2 μm or more, and most preferably 3 μm or more. The particle diameter of the resin particles is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle diameter of the resin particles is equal to or greater than the lower limit, the contact area between the conductive particles and the electrodes is increased, so that the reliability of conduction between the electrodes can be further improved, and the connection resistance between the electrodes connected via the conductive particles can be further reduced. Furthermore, when forming a conductive portion on the surface of the resin particles by electroless plating, it is possible to make it difficult for aggregated conductive particles to be formed. When the particle diameter of the resin particles is equal to or less than the upper limit, the conductive particles are easily compressed sufficiently, the connection resistance between the electrodes can be further reduced, and the distance between the electrodes can be further reduced.

[0073] When the base particle is an inorganic particle other than metal or an organic-inorganic hybrid particle, the inorganic material for forming the base particle may include silica, alumina, barium titanate, zirconia, and carbon black. The inorganic material is preferably not metal. The particle formed by the silica is not particularly limited, but may be, for example, a particle obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form a crosslinked polymer particle, and then baking it as necessary. The organic-inorganic hybrid particle may be, for example, an organic-inorganic hybrid particle formed by a crosslinked alkoxysilyl polymer and an acrylic resin.

[0074] The organic-inorganic hybrid particles are preferably core-shell type organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. From the viewpoint of effectively reducing the connection resistance between electrodes, the base particle is preferably an organic-inorganic hybrid particle having an organic core and an inorganic shell disposed on the surface of the organic core.

[0075] Examples of materials for forming the organic core include the resins for forming the resin particles described above.

[0076] The material for forming the inorganic shell includes the inorganic material for forming the base particle described above. The material for forming the inorganic shell is preferably silica. The inorganic shell is preferably formed by forming a shell-like material from a metal alkoxide on the surface of the core by a sol-gel method, and then sintering the shell-like material. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed from a silane alkoxide.

[0077] The particle diameter of the core is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 1.5 μm or more, particularly preferably 2 μm or more, most preferably 3 μm or more, and preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, most preferably 10 μm or less. When the particle diameter of the core is the above lower limit or more and the above upper limit or less, a conductive particle more suitable for electrical connection between electrodes can be obtained, and the base particle can be suitably used for the application of the conductive particle. For example, when the particle diameter of the core is the above lower limit or more and the above upper limit or less, when the conductive particle is used to connect between electrodes, the contact area between the conductive particle and the electrode becomes sufficiently large, and when the conductive part is formed, it is possible to make it difficult to form aggregated conductive particles. In addition, the gap between the electrodes connected via the conductive particle is not too large, and it is possible to make it difficult for the conductive part to peel off from the surface of the base particle.

[0078] The particle diameter of the core means the diameter when the core is spherical, and means the circle equivalent diameter when the core is other than spherical. The particle diameter of the core means the average particle diameter measured by any particle diameter measuring device. The average particle diameter is preferably the number average particle diameter. For example, a particle size distribution measuring device using the principles of laser light scattering, electrical resistance change, image analysis after imaging, etc. can be used.

[0079] The thickness of the shell is preferably 0.1 μm or more, more preferably 0.2 μm or more, and preferably 5 μm or less, more preferably 3 μm or less. When the thickness of the shell is equal to or more than the lower limit and equal to or less than the upper limit, a conductive particle more suitable for electrical connection between electrodes is obtained, and the base particle can be suitably used for the application of the conductive particle. The thickness of the shell is the average thickness per base particle. The thickness of the shell can be controlled by controlling the sol-gel method.

[0080] The particle diameter of the inorganic particles other than the metal particles and the organic-inorganic hybrid particles is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 1.5 μm or more, particularly preferably 2 μm or more, and most preferably 3 μm or more. The particle diameter of the inorganic particles other than the metal particles and the organic-inorganic hybrid particles is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle diameter of the inorganic particles other than the metal particles and the organic-inorganic hybrid particles is the above lower limit or more and the above upper limit or less, the contact area between the conductive particles and the electrodes is large, so that the conduction reliability between the electrodes can be further improved, and the connection resistance between the electrodes connected via the conductive particles can be further reduced. Furthermore, when forming a conductive portion on the surface of the inorganic particles other than the metal particles or the organic-inorganic hybrid particles by electroless plating, it is possible to make it difficult for aggregated conductive particles to be formed. When the particle size of the organic-inorganic hybrid particles is equal to or less than the upper limit, the conductive particles are easily compressed sufficiently, the connection resistance between the electrodes can be further reduced, and the distance between the electrodes can be further reduced.

[0081] When the base particles are metal particles, examples of the metal that is the material of the metal particles include silver, copper, nickel, silicon, gold, and titanium.

[0082] The particle diameter of the metal particles is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 1.5 μm or more, particularly preferably 2 μm or more, and most preferably 3 μm or more. The particle diameter of the metal particles is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle diameter of the metal particles is the above lower limit or more and the above upper limit or less, the contact area between the conductive particles and the electrodes is large, so that the reliability of conduction between the electrodes can be further improved, and the connection resistance between the electrodes connected via the conductive particles can be further reduced. Furthermore, when forming a conductive portion on the surface of the resin particles by electroless plating, it is possible to make it difficult for aggregated conductive particles to be formed.

[0083] The particle diameter of the base particle is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 1.5 μm or more, particularly preferably 2 μm or more, and most preferably 3 μm or more. The particle diameter of the base particle is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle diameter of the base particle is the above lower limit or more, the contact area between the conductive particles and the electrodes is increased, so that the reliability of conduction between the electrodes can be further improved, and the connection resistance between the electrodes connected via the conductive particles can be further reduced. Furthermore, when forming a conductive portion on the surface of the base particle by electroless plating, it is possible to make it difficult for aggregated conductive particles to be formed. When the particle diameter of the base particle is the above upper limit or less, the conductive particles are easily compressed sufficiently, the connection resistance between the electrodes can be further reduced, and the gap between the electrodes can be further reduced.

[0084] The particle diameter of the base particle refers to the diameter when the base particle is spherical, and refers to the circle equivalent diameter when the base particle is not spherical. The particle diameter of the base particle refers to the average particle diameter measured by any particle diameter measuring device. The average particle diameter is preferably a number average particle diameter. For example, a particle size distribution measuring device using the principles of laser light scattering, electrical resistance change, image analysis after imaging, etc. can be used.

[0085] The particle diameter of the base particle is particularly preferably 2 μm or more and 20 μm or less. When the particle diameter of the base particle is in the range of 2 μm or more and 20 μm or less, the distance between the electrodes can be made smaller, and even if the thickness of the conductive part is increased, small conductive particles can be obtained.

[0086] (First conductive portion and second conductive portion) In the conductive particle according to the present invention, the first conductive part contains nickel and boron, but does not contain phosphorus. In the conductive particle according to the present invention, the absolute value of the difference between the average content of boron in 100% by weight of the region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive part toward the outside and the average content of boron in 100% by weight of the region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive part toward the inside is 0% by weight or more and 10% by weight or less. When the first conductive part has a single-layer structure, the region (R1) is the region between the inner surface of the first conductive part 3 (the outer surface of the base particle 2) and the dashed line L1 in FIG. 5. When the first conductive part has a single-layer structure, the region (R2) is the region between the outer surface of the first conductive part 3 (the inner surface of the second conductive part 4) and the dashed line L2 in FIG. 5. When the first conductive portion has a two-layer structure, the region (R1) is the region between the inner surface of the first conductive portion 13 (the inner surface of the conductive portion 13A, the outer surface of the base particle 2) and the dashed line L1 in FIG. 6. When the first conductive portion has a two-layer structure, the region (R2) is the region between the outer surface of the first conductive portion 13 (the outer surface of the conductive portion 13B, the inner surface of the second conductive portion 4) and the dashed line L2 in FIG. 6. When the first conductive portion has a multi-layer structure of two or more layers, the region (R1) and the region (R2) are preferably calculated from the thickness of the entire first conductive portion.

[0087] The absolute value of the difference between the average boron content in 100 weight % of the region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive part toward the outside and the average boron content in 100 weight % of the region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive part toward the inside may be more than 0 weight % or may be 0.5 weight % or more. The absolute value of the difference between the average boron content in 100 weight % of the region (R1) and the average boron content in 100 weight % of the region (R2) is preferably 1.0 weight % or more. When the absolute value of the difference between the average boron content in 100 weight % of the region (R1) and the average boron content in 100 weight % of the region (R2) is equal to or more than the lower limit, the occurrence of cracks in the conductive part during mounting can be more effectively suppressed. The absolute value of the difference between the average boron content in 100 weight percent of the region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive part toward the outside and the average boron content in 100 weight percent of the region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive part toward the inside is preferably 5 weight percent or less. When the absolute value of the difference between the average boron content in 100 weight percent of the region (R1) and the average boron content in 100 weight percent of the region (R2) is equal to or less than the upper limit, the occurrence of cracks in the conductive part during mounting can be more effectively suppressed, and the connection resistance between the electrodes can be more effectively reduced.

[0088] The average content of boron in 100% by weight of the region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive part toward the outside is preferably 0% by weight or more, more preferably 0.001% by weight or more, even more preferably 0.01% by weight or more, and particularly preferably 0.1% by weight or more. The average content of boron in 100% by weight of the region (R1) having a thickness of 1 / 5 from the inner surface of the first conductive part toward the outside is preferably 10% by weight or less, more preferably 5% by weight or less, even more preferably 4% by weight or less, and particularly preferably 3% by weight or less. When the average content of boron in 100% by weight of the region (R1) is the above lower limit or more and the above upper limit or less, the occurrence of cracks in the conductive part during mounting can be more effectively suppressed, and the connection resistance between the electrodes can be more effectively reduced. The region having an average content of boron of 0% by weight does not contain boron.

[0089] The average content of boron in 100% by weight of the region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive part toward the inside is preferably 0% by weight or more, more preferably 0.001% by weight or more, even more preferably 0.01% by weight or more, and particularly preferably 0.1% by weight or more. The average content of boron in 100% by weight of the region (R2) having a thickness of 1 / 5 from the outer surface of the first conductive part toward the inside is preferably 10% by weight or less, more preferably 5% by weight or less, even more preferably 4% by weight or less, and particularly preferably 3% by weight or less. When the average content of boron in 100% by weight of the region (R2) is the above lower limit or more and the above upper limit or less, the occurrence of cracks in the conductive part during mounting can be more effectively suppressed, and the connection resistance between the electrodes can be more effectively reduced.

[0090] From the viewpoint of more effectively suppressing the occurrence of cracks in the conductive portion during mounting and more effectively reducing the connection resistance between electrodes, it is preferable that boron be uniformly distributed in the first conductive portion.

[0091] The average nickel content in the first conductive part (100% by weight) is preferably 50% by weight or more, more preferably 65% ​​by weight or more, and preferably 99.9% by weight or less, more preferably 95% by weight or less. When the average nickel content in the first conductive part (100% by weight) is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of cracks in the conductive part during mounting can be more effectively suppressed, and the connection resistance between the electrodes can be more effectively reduced.

[0092] The average content of boron in 100% by weight of the first conductive part is preferably 0.001% by weight or more, more preferably 0.01% by weight or more, even more preferably 0.1% by weight or more, and is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less. When the average content of boron in 100% by weight of the first conductive part is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of cracks in the conductive part during mounting can be more effectively suppressed, and the connection resistance between the electrodes can be more effectively reduced.

[0093] The method for measuring the average contents of nickel and boron in the first conductive part is not particularly limited and may use various known analytical methods. Examples of the measuring method include absorption spectrometry and spectral analysis. In the absorption spectrometry, a flame absorption spectrometer and an electric heating furnace absorption spectrometer may be used. Examples of the spectral analysis include plasma emission spectrometry and plasma ion source mass spectrometry.

[0094] When measuring the average contents of nickel and boron in the first conductive part, it is preferable to use an ICP optical emission spectrometer. Commercially available ICP optical emission spectrometers include an ICP optical emission spectrometer manufactured by HORIBA and an ICP-MS manufactured by Hitachi High-Tech Science Corporation. When measuring the average contents of nickel and boron in the first conductive part after forming the second conductive part, the measurements can be performed by an energy dispersive X-ray spectrometer (EDS) using a field emission transmission electron microscope (JEM-2010FEF manufactured by JEOL Ltd.).

[0095] When measuring the respective contents and respective average contents of nickel and boron in each region in the thickness direction of the first conductive portion, the measurements can be performed using an energy dispersive X-ray analyzer (EDS) using a field emission transmission electron microscope (JEM-2010FEF manufactured by JEOL Ltd.) or the like.

[0096] The thickness of the first conductive part is preferably 0.005 μm or more, more preferably 0.01 μm or more, even more preferably 0.05 μm or more, and is preferably 1 μm or less, more preferably 0.3 μm or less. When the thickness of the first conductive part is equal to or more than the lower limit and equal to or less than the upper limit, sufficient conductivity can be obtained, and the conductive particles do not become too hard, so that the conductive particles can be sufficiently deformed when connecting between electrodes. When the first conductive part has a multi-layer structure of two or more layers, the thickness of the first conductive part is preferably the total thickness of all layers.

[0097] The thickness of the first conductive part is particularly preferably 0.05 μm or more and 0.3 μm or less. Furthermore, it is particularly preferably that the particle diameter of the base particle is 2 μm or more and 20 μm or less, and the thickness of the first conductive part is 0.05 μm or more and 0.3 μm or less. In this case, the conductive particles can be more suitably used in applications where a large current flows. Furthermore, when the conductive particles are compressed to connect the electrodes, damage to the electrodes can be further suppressed.

[0098] The thickness of the second conductive part is preferably 0.005 μm or more, more preferably 0.01 μm or more, and even more preferably 0.02 μm or more, and is preferably 1 μm or less, and more preferably 0.3 μm or less. When the thickness of the second conductive part is equal to or more than the lower limit and equal to or less than the upper limit, sufficient conductivity can be obtained, and the conductive particles do not become too hard, so that the conductive particles can be sufficiently deformed when connecting the electrodes.

[0099] The thickness of the second conductive part is particularly preferably 0.02 μm or more and 0.3 μm or less. Furthermore, it is particularly preferably that the particle diameter of the base particle is 2 μm or more and 20 μm or less, and the thickness of the second conductive part is 0.02 μm or more and 0.3 μm or less. In this case, the conductive particles can be more suitably used in applications where a large current flows. Furthermore, when the conductive particles are compressed to connect the electrodes, damage to the electrodes can be further suppressed.

[0100] The thickness of the first conductive portion and the thickness of the second conductive portion can be measured by observing a cross section of the conductive particle using, for example, a transmission electron microscope ("JEM-2100" manufactured by JEOL Ltd.).

[0101] The first conductive part preferably contains nickel as a main metal. The first conductive part may contain a metal other than nickel. Examples of the metal other than nickel in the first conductive part include gold, silver, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, palladium, chromium, seaborgium, titanium, antimony, bismuth, thallium, tungsten, germanium, cadmium, silicon, molybdenum, tin-doped indium oxide (ITO), and solder. Only one of these metals may be used, or two or more of them may be used in combination. When the first conductive part contains multiple metals, the multiple metals may be alloyed.

[0102] The metal for forming the second conductive part is not particularly limited. Examples of the metal include gold, silver, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, palladium, chromium, ruthenium, rhodium, iridium, bismuth, thallium, tungsten, germanium, cadmium, silicon, and molybdenum. From the viewpoint of more effectively lowering the connection resistance between electrodes, the metal preferably has a higher potential than nickel, which is the main metal of the first conductive part. The metal is preferably tin, copper, palladium, ruthenium, platinum, silver, rhodium, iridium, or gold, and more preferably gold, silver, copper, or palladium. From the viewpoint of more effectively lowering the connection resistance between electrodes, the main metal in the second conductive part is preferably tin, copper, palladium, ruthenium, platinum, silver, rhodium, iridium, or gold, and more preferably gold or palladium. From the viewpoint of more effectively suppressing the occurrence of cracks in the conductive portion during mounting, the main metal in the second conductive portion is preferably palladium or ruthenium, and more preferably palladium.

[0103] The main metal in the first conductive part and the main metal in the second conductive part refer to the metal with the largest content among the metals contained in the first conductive part and the second conductive part. The content of the main metal in 100% by weight of all metals contained in the first conductive part and the second conductive part is preferably 50% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. The first conductive part and the second conductive part may contain only one type of metal, or may contain two or more types of metals.

[0104] The method of forming the first conductive part and the second conductive part is not particularly limited. Examples of the method of forming the first conductive part and the second conductive part include a method using electroless plating, a method using electroplating, a method using physical vapor deposition, and a method of coating a metal powder or a paste containing a metal powder and a binder on the surface of a base particle or other conductive part. Since the conductive part is easily formed, a method using electroless plating is preferred. Examples of the method using physical vapor deposition include vacuum deposition, ion plating, and ion sputtering.

[0105] The particle diameter of the conductive particles is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 1.5 μm or more, particularly preferably 2 μm or more, and most preferably 3 μm or more. The particle diameter of the conductive particles is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, when the conductive particles are used to connect electrodes, the contact area between the conductive particles and the electrodes can be sufficiently large, and when forming the conductive part, it is possible to make it difficult for aggregated conductive particles to be formed. In addition, the gap between the electrodes connected via the conductive particles is not too large, and it is possible to make it difficult for the conductive part to peel off from the surface of the base particle.

[0106] The particle diameter of the conductive particles indicates the diameter when the conductive particles are spherical, and indicates the circle-equivalent diameter when the conductive particles are not spherical. The particle diameter of the conductive particles is preferably an average particle diameter, and more preferably a number-average particle diameter. The particle diameter of the conductive particles is obtained, for example, by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average particle diameter of each conductive particle, or by performing laser diffraction particle size distribution measurement. In the observation with an electron microscope or an optical microscope, the particle diameter of each conductive particle is obtained as the particle diameter of the circle-equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary conductive particles with the circle-equivalent diameter is almost equal to the average particle diameter of the sphere-equivalent diameter. In the laser diffraction particle size distribution measurement, the particle diameter of each conductive particle is obtained as the particle diameter of the sphere-equivalent diameter. The particle diameter of the conductive particles is preferably calculated by laser diffraction particle size distribution measurement.

[0107] Methods for controlling the respective contents and respective average contents of nickel and boron in each region of the first conductive portion include, for example, a method for controlling the pH of a nickel plating solution when forming the first conductive portion by electroless nickel plating, a method for adjusting the boron concentration in a nickel plating solution, and a method for adjusting the nickel concentration in a nickel plating solution.

[0108] In the method of forming by electroless plating, generally, a catalysis step and an electroless plating step are performed. Hereinafter, an example of a method of forming a first conductive portion containing nickel and boron on the surface of a base particle by electroless plating will be described.

[0109] In the catalysis step, a catalyst that serves as a starting point for forming a plating layer by electroless plating is formed on the surface of the base particle.

[0110] Examples of methods for forming the catalyst on the surface of the base particle include the following methods. A method in which the base particle is added to a solution containing palladium chloride and tin chloride, and then the surface of the base particle is activated with an acid solution or an alkaline solution to precipitate palladium on the surface of the base particle. A method in which the base particle is added to a solution containing palladium sulfate and aminopyridine, and then the surface of the base particle is activated with a solution containing a reducing agent to precipitate palladium on the surface of the base particle. A boron-containing reducing agent is used as the reducing agent. In addition, by using a boron-containing reducing agent as the reducing agent, a first conductive portion containing boron can be formed.

[0111] In the electroless plating step, a nickel plating bath containing a nickel-containing compound, a boron-containing reducing agent, and, if necessary, a complexing agent and a stabilizer is suitably used.

[0112] By immersing the base particles in a nickel plating bath, nickel can be precipitated on the surface of the base particles having a catalyst formed on the surface, and a first conductive portion containing nickel and boron can be formed.

[0113] The nickel-containing compound includes nickel sulfate, nickel chloride, etc. The nickel-containing compound is preferably a nickel salt.

[0114] The boron-containing reducing agent includes dimethylamine borane, sodium borohydride, potassium borohydride, and the like.

[0115] Examples of the complexing agent include monocarboxylic acid complexing agents such as sodium acetate and sodium propionate, dicarboxylic acid complexing agents such as disodium malonate, tricarboxylic acid complexing agents such as disodium succinate, hydroxy acid complexing agents such as lactic acid, DL-malic acid, Rochelle salt, sodium citrate, and sodium gluconate, amino acid complexing agents such as glycine and EDTA, amine complexing agents such as ethylenediamine, organic acid complexing agents such as maleic acid, and salts thereof. Only one type of the complexing agent may be used, or two or more types may be used in combination.

[0116] As the stabilizer, a lead compound, a bismuth compound, or a thallium compound may be added. Specific examples of these compounds include sulfates, carbonates, acetates, nitrates, and hydrochlorides of the metals (lead, bismuth, and thallium) that constitute the compounds. In consideration of the impact on the environment, bismuth compounds and thallium compounds are preferable.

[0117] Preferred examples of the method for increasing the boron content in the first conductive portion include a method for lowering the pH of the plating solution to slow down the reaction rate of the nickel plating solution, a method for lowering the temperature of the nickel plating solution, a method for increasing the concentration of a boron-containing reducing agent in the nickel plating solution, and a method for increasing the concentration of a complexing agent in the nickel plating solution. These methods may be used alone or in combination of two or more. The above preferred methods can adjust the average boron content in 100% by weight of the region (R1) and the average boron content in 100% by weight of the region (R2). As a result, it becomes easy to set the absolute value of the difference between the average boron content in 100% by weight of the region (R1) and the average boron content in 100% by weight of the region (R2) to be 0% by weight or more and 10% by weight or less.

[0118] (core substance) The conductive particles preferably have protrusions on their conductive surfaces. The first conductive part or the second conductive part preferably has protrusions on its outer surface. The first conductive part and the second conductive part preferably have protrusions on their outer surfaces. The protrusions are preferably multiple. An oxide film is often formed on the surface of the electrodes connected by the conductive particles. Furthermore, an oxide film is often formed on the surface of the conductive part of the conductive particles. By using the conductive particles having the protrusions, the oxide film is effectively removed by the protrusions when the conductive particles are placed between the electrodes and then pressed together. Therefore, the electrodes and the conductive particles can be more reliably contacted, and the connection resistance between the electrodes can be reduced. Furthermore, when the conductive particles have an insulating material on their surfaces, or when the conductive particles are dispersed in a binder resin and used as a conductive material, the protrusions of the conductive particles can effectively remove the insulating material or binder resin between the conductive particles and the electrodes. Therefore, the reliability of conduction between the electrodes can be improved.

[0119] In addition, when the conductive particles have protrusions on the outer surface of the first conductive part or the second conductive part, the area of ​​contact between the conductive particles can be reduced. Therefore, the aggregation of the conductive particles can be suppressed. Therefore, electrical connection between electrodes that should not be connected can be prevented, and the insulation reliability can be further improved.

[0120] The core material is embedded in the first conductive part or the second conductive part, so that the first conductive part or the second conductive part can easily have a plurality of protrusions on the outer surface. From the viewpoint of easily forming a plurality of protrusions, it is preferable to provide a plurality of core materials that raise the surface of the first conductive part or the second conductive part so as to form a plurality of protrusions inside or on the inside of the first conductive part or the second conductive part. However, it is not necessary to use a core material to form protrusions on the outer surfaces of the conductive particle, the first conductive part, and the second conductive part, and it is preferable not to use a core material. It is preferable that the conductive particle does not have a core material for raising the outer surfaces of the first conductive part and the second conductive part. It is preferable that the conductive particle does not have a plurality of core materials that raise the surface of the first conductive part or the second conductive part so as to form a plurality of protrusions inside or on the inside of the first conductive part or the second conductive part. When the core material is used, the core material is preferably disposed inside or within the first conductive part. When the core material is used, the core material may be disposed inside or within the second conductive part.

[0121] Methods for forming the protrusions include the following: A method in which a core substance is attached to the surface of a base particle, and then a conductive portion is formed by electroless plating. A method in which a conductive portion is formed on the surface of a base particle by electroless plating, and then a core substance is attached, and then a conductive portion is formed by electroless plating. A method in which a core substance is added during the process of forming a conductive portion on the surface of a base particle by electroless plating.

[0122] Examples of methods for disposing a core substance on the surface of the base particle include the following methods. A method in which a core substance is added to a dispersion of base particles, and the core substance is accumulated and adhered to the surface of the base particle by van der Waals forces or the like. A method in which a core substance is added to a container containing base particles, and the core substance is adhered to the surface of the base particle by mechanical action such as rotation of the container. Since the amount of core substance to be adhered is easy to control, the method for disposing a core substance on the surface of the base particle is preferably a method in which the core substance is accumulated and adhered to the surface of the base particle in the dispersion.

[0123] The core material may be a conductive material or a non-conductive material. The conductive material may be, for example, a conductive non-metal such as metal, metal oxide, graphite, or a conductive polymer. The conductive polymer may be polyacetylene. The non-conductive material may be silica, alumina, barium titanate, zirconia, or the like. In order to effectively eliminate the oxide film, it is preferable that the core material is hard. Metals are preferable because they can increase the conductivity and effectively reduce the connection resistance. The core material is preferably a metal particle. As the metal material of the core material, the metals listed as the materials of the first conductive part and the second conductive part can be appropriately used.

[0124] Examples of the material of the core material include barium titanate (Mohs hardness 4.5), nickel (Mohs hardness 5), silica (silicon dioxide, Mohs hardness 6 to 7), titanium oxide (Mohs hardness 7), zirconia (Mohs hardness 8 to 9), alumina (Mohs hardness 9), tungsten carbide (Mohs hardness 9), and diamond (Mohs hardness 10). From the viewpoint of more effectively increasing the conductivity and more effectively decreasing the connection resistance, the core material is preferably nickel, silica, titanium oxide, zirconia, alumina, tungsten carbide, or diamond, and more preferably silica, titanium oxide, zirconia, alumina, tungsten carbide, or diamond. From the viewpoint of more effectively increasing the conductivity and more effectively decreasing the connection resistance, the core material is more preferably titanium oxide, zirconia, alumina, tungsten carbide, or diamond, and particularly preferably zirconia, alumina, tungsten carbide, or diamond. From the viewpoint of more effectively increasing the electrical conductivity and more effectively reducing the connection resistance, the Mohs hardness of the core material is preferably 5 or more, more preferably 6 or more, even more preferably 7 or more, and particularly preferably 7.5 or more.

[0125] The shape of the core material is not particularly limited. The core material is preferably in the form of a mass. Examples of the core material include particulate masses, aggregates of a plurality of microparticles, and amorphous masses.

[0126] The particle size of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, and is preferably 1 μm or less, more preferably 0.5 μm or less. When the particle size of the core material is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be effectively reduced.

[0127] The particle size of the core material indicates the diameter when the core material is spherical, and indicates the circle-equivalent diameter when the core material is not spherical. The particle size of the core material is preferably the average particle size, and more preferably the number-average particle size. The particle size of the core material is determined, for example, by observing 50 arbitrary core materials with an electron microscope or optical microscope, and calculating the average particle size of each core material, or by performing laser diffraction particle size distribution measurement. In the observation with an electron microscope or optical microscope, the particle size of each core material is determined as the particle size at the circle-equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle size of 50 arbitrary core materials at the circle-equivalent diameter is almost equal to the average particle size at the sphere-equivalent diameter. In the laser diffraction particle size distribution measurement, the particle size of each core material is determined as the particle size at the sphere-equivalent diameter. The particle size of the core material is preferably calculated by laser diffraction particle size distribution measurement.

[0128] The number of the protrusions per conductive particle is preferably 3 or more, more preferably 5 or more. The upper limit of the number of the protrusions is not particularly limited. The upper limit of the number of the protrusions can be appropriately selected in consideration of the particle diameter of the conductive particles, etc. When the average height of the protrusions is equal to or greater than the lower limit, the connection resistance between the electrodes can be more effectively reduced.

[0129] The average height of the plurality of protrusions is preferably 0.001 μm or more, more preferably 0.05 μm or more, and is preferably 1 μm or less, more preferably 0.5 μm or less. When the average height of the protrusions is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be reduced more effectively.

[0130] (Insulating material) The conductive particles preferably comprise an insulating material disposed on the outer surface of the second conductive part. In this case, when the conductive particles are used for connecting electrodes, short-circuiting between adjacent electrodes can be further prevented. Specifically, when a plurality of conductive particles come into contact with each other, an insulating material is present between the plurality of electrodes, so that short-circuiting between horizontally adjacent electrodes, rather than between upper and lower electrodes, can be prevented. In addition, when connecting electrodes, the insulating material between the second conductive part and the electrode can be easily removed by pressing the conductive particles with the two electrodes. When the conductive particles have a plurality of protrusions on the outer surface of the second conductive part, the insulating material between the second conductive part and the electrode can be more easily removed.

[0131] The insulating material is preferably insulating particles, since this makes it easier to remove the insulating material when the electrodes are pressed together. The insulating material may be an insulating layer.

[0132] The material of the insulating material includes the above-mentioned resin particle material and the above-mentioned inorganic material as the material of the base particle. The material of the insulating material is preferably the above-mentioned resin particle material. The insulating material is preferably the above-mentioned resin particle or the above-mentioned organic-inorganic hybrid particle, and may be the above-mentioned resin particle or the above-mentioned organic-inorganic hybrid particle.

[0133] Other materials for the insulating material include polyolefin compounds, (meth)acrylate polymers, (meth)acrylate copolymers, block polymers, thermoplastic resins, crosslinked products of thermoplastic resins, thermosetting resins, water-soluble resins, etc. Only one type of the insulating material may be used, or two or more types may be used in combination.

[0134] Examples of the polyolefin compound include polyethylene, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid ester copolymer. Examples of the (meth)acrylate polymer include polymethyl (meth)acrylate, polydodecyl (meth)acrylate, and polystearyl (meth)acrylate. Examples of the block polymer include polystyrene, styrene-acrylic acid ester copolymer, SB type styrene-butadiene block copolymer, SBS type styrene-butadiene block copolymer, and hydrogenated products thereof. Examples of the thermoplastic resin include vinyl polymers and vinyl copolymers. Examples of the thermosetting resin include epoxy resin, phenolic resin, and melamine resin. Examples of the crosslinked thermoplastic resin include the introduction of polyethylene glycol methacrylate, alkoxylated trimethylolpropane methacrylate, and alkoxylated pentaerythritol methacrylate. Examples of the water-soluble resin include polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyvinylpyrrolidone, polyethylene oxide, and methyl cellulose. In addition, a chain transfer agent may be used to adjust the degree of polymerization. Examples of the chain transfer agent include thiol and carbon tetrachloride.

[0135] Methods for disposing an insulating material on the outer surface of the second conductive part include chemical methods and physical or mechanical methods. Examples of the chemical methods include interfacial polymerization, suspension polymerization in the presence of particles, and emulsion polymerization. Examples of the physical or mechanical methods include spray drying, hybridization, electrostatic adhesion, spraying, dipping, and vacuum deposition. Since the insulating material is difficult to remove, a method in which the insulating material is disposed on the surface of the second conductive part via a chemical bond is preferred.

[0136] It is preferable that a polar group such as a hydroxyl group is present on the surface of the insulating material. The presence of the polar group allows the continuous film described below to cover the surface of the insulating material more uniformly.

[0137] The outer surface of the second conductive part and the surface of the insulating particle may each be coated with a compound having a reactive functional group. The outer surface of the second conductive part and the surface of the insulating particle may not be directly chemically bonded, and may be indirectly chemically bonded by a compound having a reactive functional group. After introducing a carboxyl group into the outer surface of the second conductive part, the carboxyl group may be chemically bonded to the functional group on the surface of the insulating particle via a polymer electrolyte such as polyethyleneimine.

[0138] When the insulating material is insulating particles, the particle size of the insulating particles can be appropriately selected depending on the particle size of the conductive particles and the application. The particle size of the insulating particles is preferably 10 nm or more, more preferably 100 nm or more, and preferably 4000 nm or less, more preferably 2000 nm or less. If the particle size of the insulating particles is equal to or greater than the lower limit, the conductive parts of the conductive particles are less likely to contact each other when the conductive particles are dispersed in the binder resin. If the particle size of the insulating particles is equal to or less than the upper limit, there is no need to apply too much pressure or heat to a high temperature in order to remove the insulating particles between the electrodes and the conductive particles when connecting the electrodes.

[0139] The particle diameter of the insulating particles indicates the diameter when the insulating particles are spherical, and indicates the circle-equivalent diameter when the insulating particles are not spherical. The particle diameter of the insulating particles is preferably an average particle diameter, and more preferably a number-average particle diameter. The particle diameter of the insulating particles is obtained, for example, by observing 50 arbitrary insulating particles with an electron microscope or an optical microscope and calculating the average particle diameter of each insulating particle, or by performing laser diffraction particle size distribution measurement. In the observation with an electron microscope or an optical microscope, the particle diameter of each insulating particle is obtained as the particle diameter of the circle-equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary insulating particles with the circle-equivalent diameter is almost equal to the average particle diameter of the sphere-equivalent diameter. In the laser diffraction particle size distribution measurement, the particle diameter of each insulating particle is obtained as the particle diameter of the sphere-equivalent diameter. The particle diameter of the insulating particles is preferably calculated by laser diffraction particle size distribution measurement. In addition, when the particle size of the insulating particles in the conductive particles is measured, the measurement can be performed, for example, as follows.

[0140] Conductive particles are added to Kulzer's Technovit 4000 so that the content is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. A cross section of the conductive particles is cut out using an ion milling device (Hitachi High-Technologies' IM4000) so as to pass through the center of the dispersed conductive particles in the resin body for inspection. Then, using a field emission scanning electron microscope (FE-SEM) set to an image magnification of 50,000 times, 50 conductive particles are randomly selected, and the insulating particles in each conductive particle are observed. The particle diameter of the insulating particles in each conductive particle is measured, and the particle diameter of the insulating particles is determined by arithmetic averaging.

[0141] When the insulating material is an insulating particle, the ratio of the particle diameter of the conductive particle to the particle diameter of the insulating particle (particle diameter of conductive particle / particle diameter of insulating particle) is preferably 3 or more, more preferably 5 or more, even more preferably 8 or more, even more preferably 10 or more, and particularly preferably 12 or more. When the insulating material is an insulating particle, the ratio of the particle diameter of the conductive particle to the particle diameter of the insulating particle (particle diameter of conductive particle / particle diameter of insulating particle) is preferably 1000 or less, more preferably 100 or less, even more preferably 75 or less, even more preferably 50 or less, and particularly preferably 30 or less. When the ratio (particle diameter of conductive particle / particle diameter of insulating particle) is equal to or more than the lower limit and equal to or less than the upper limit, the insulating particles can be more uniformly arranged on the outer surface of the second conductive part, and the insulation reliability between the electrodes can be more effectively improved.

[0142] (Continuous film) When the conductive particles include the insulating material, the conductive particles preferably include a continuous film containing an inorganic material. The continuous film preferably has a portion covering the surface of the second conductive part and a portion covering the surface of the insulating material. In the conductive particles, the surface of the second conductive part and the surface of the insulating material are preferably covered by the continuous film, and it is preferable that the continuous film covering the surface of the second conductive part and the continuous film covering the insulating material are connected. In this case, it is possible to more effectively prevent the insulating material from being unintentionally detached from the surface of the conductive particles before conductive connection such as dispersing the conductive particles in a binder resin. As a result, it is possible to more effectively improve the insulation reliability between adjacent electrodes.

[0143] From the viewpoint of more effectively increasing the insulation reliability between the electrodes and more effectively increasing the conduction reliability between the electrodes, the continuous film is preferably an inorganic oxide film. The continuous film is preferably formed of an inorganic material. In this case, when the electrodes are electrically connected using the conductive particles, the insulating material can be more easily detached from the surface of the conductive particles. As a result, the conduction reliability between the electrodes can be more effectively increased.

[0144] Examples of the inorganic material and the material of the inorganic oxide film include oxides of silicon, titanium, zirconium, aluminum, etc., and composites of these oxides.

[0145] From the viewpoint of more effectively increasing the insulation reliability between electrodes and more effectively increasing the conduction reliability between electrodes, the thickness of the continuous film is preferably 1 nm or more, more preferably 10 nm or more, and is preferably 500 nm or less, more preferably 100 nm or less. When the continuous film has a multilayer structure of two or more layers, the thickness of the continuous film is preferably the total thickness of all layers.

[0146] The thickness of the continuous film is preferably determined by observing 50 random conductive particles under an electron microscope and calculating the average value. When measuring the thickness of the continuous film on the conductive particles, for example, it can be measured as follows.

[0147] Conductive particles are added to Kulzer's Technovit 4000 so that the content is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the dispersed conductive particles in the resin body for inspection. Then, a field emission scanning electron microscope (FE-SEM) is used to set the image magnification to 50,000 times, and 50 conductive particles are randomly selected to observe the continuous film on each conductive particle. The thickness of the continuous film on each conductive particle is measured, and the arithmetic average of the measured values ​​is determined as the thickness of the continuous film.

[0148] When the insulating material is insulating particles, the ratio of the thickness of the continuous film to the particle diameter of the insulating particles (thickness of the continuous film / particle diameter of the insulating particles) is preferably 0.01 or more, more preferably 0.05 or more, and preferably 1 or less, more preferably 0.1 or less. When the ratio (thickness of the continuous film / particle diameter of the insulating particles) is equal to or more than the lower limit and equal to or less than the upper limit, the insulation reliability between the electrodes can be more effectively improved, and the conduction reliability between the electrodes can be more effectively improved.

[0149] Methods for covering the surface of the second conductive part and the surface of the insulating material with the continuous film include a method of coating the surface of the second conductive part and the surface of the insulating material with an insulating composition (a composition containing a metal alkoxide) using a hydrolysis reaction of an alkoxide.

[0150] (Anti-rust treatment) From the viewpoint of suppressing corrosion of the conductive particles and further reducing the connection resistance between the electrodes, it is preferable that the outer surface of the second conductive portion is subjected to an anti-rust treatment.

[0151] From the viewpoint of further improving the reliability of conduction, it is preferable that the outer surface of the second conductive part is rust-proofed with a compound having an alkyl group with 6 to 22 carbon atoms. The outer surface of the second conductive part may be rust-proofed with a compound that does not contain phosphorus, or may be rust-proofed with a compound that has an alkyl group with 6 to 22 carbon atoms and does not contain phosphorus. From the viewpoint of further improving the reliability of conduction, it is preferable that the outer surface of the second conductive part is rust-proofed with an alkyl phosphate compound or an alkylthiol. By the rust-proofing, an anti-rust film can be formed on the outer surface of the second conductive part.

[0152] The anticorrosive film is preferably formed of a compound having an alkyl group with 6 to 22 carbon atoms (hereinafter also referred to as compound A). The outer surface of the second conductive part is preferably surface-treated with compound A. When the alkyl group has 6 or more carbon atoms, rust is more unlikely to occur in the entire second conductive part. When the alkyl group has 22 or less carbon atoms, the conductivity of the conductive particles is increased. From the viewpoint of further increasing the conductivity of the conductive particles, the alkyl group in compound A preferably has 16 or less carbon atoms. The alkyl group may have a straight-chain structure or a branched structure. The alkyl group preferably has a straight-chain structure.

[0153] The compound A is not particularly limited as long as it has an alkyl group having 6 to 22 carbon atoms. The compound A is preferably a phosphate ester or a salt thereof having an alkyl group having 6 to 22 carbon atoms, a phosphite ester or a salt thereof having an alkyl group having 6 to 22 carbon atoms, or an alkoxysilane having an alkyl group having 6 to 22 carbon atoms. The compound A is preferably an alkylthiol having an alkyl group having 6 to 22 carbon atoms, or a dialkyl disulfide having an alkyl group having 6 to 22 carbon atoms. The compound A having an alkyl group having 6 to 22 carbon atoms is preferably a phosphate ester or a salt thereof, a phosphite ester or a salt thereof, an alkoxysilane, an alkylthiol, or a dialkyl disulfide. By using these preferable compounds A, it is possible to make the second conductive portion more unlikely to rust. From the viewpoint of making it more unlikely to rust, the compound A is preferably the phosphate ester or a salt thereof, the phosphite ester or a salt thereof, or an alkylthiol, and more preferably the phosphate ester or a salt thereof, or the phosphite ester or a salt thereof. The compound A may be used alone or in combination of two or more kinds.

[0154] The compound A preferably has a reactive functional group capable of reacting with the outer surface of the second conductive part. The compound A preferably has a reactive functional group capable of reacting with the insulating material. The rust-preventive film is preferably chemically bonded to the second conductive part. The rust-preventive film is preferably chemically bonded to the insulating material. The rust-preventive film is more preferably chemically bonded to both the second conductive part and the insulating material. The presence of the reactive functional group and the chemical bond make the rust-preventive film less likely to peel off, and as a result, rust is more unlikely to occur on the second conductive part, and the insulating material is more unlikely to unintentionally detach from the surface of the conductive particle.

[0155] Examples of the phosphoric acid ester or salt thereof having an alkyl group having 6 to 22 carbon atoms include hexyl phosphate, heptyl phosphate, monooctyl phosphate, monononyl phosphate, monodecyl phosphate, monoundecyl phosphate, monododecyl phosphate, monotridecyl phosphate, monotetradecyl phosphate, monopentadecyl phosphate, monohexyl ester monosodium salt, monoheptyl phosphate, monooctyl phosphate, monononyl ester monosodium salt, monodecyl phosphate, monoundecyl phosphate, monododecyl phosphate, monotridecyl ester monosodium salt, monotetradecyl phosphate, monopentadecyl ester monosodium salt, etc. Potassium salts of the above phosphoric acid esters may also be used.

[0156] Examples of the phosphorous acid ester or salt thereof having an alkyl group having 6 to 22 carbon atoms include hexyl phosphorous acid ester, heptyl phosphorous acid ester, monooctyl phosphorous acid ester, monononyl phosphorous acid ester, monodecyl phosphorous acid ester, monoundecyl phosphorous acid ester, monododecyl phosphorous acid ester, monotridecyl phosphorous acid ester, monotetradecyl phosphorous acid ester, monopentadecyl phosphorous acid ester, monohexyl phosphorous acid ester monosodium salt, monoheptyl phosphorous acid ester monosodium salt, monooctyl phosphorous acid ester monosodium salt, monononyl phosphorous acid ester monosodium salt, monodecyl phosphorous acid ester monosodium salt, monoundecyl phosphorous acid ester monosodium salt, monododecyl phosphorous acid ester monosodium salt, monotridecyl phosphorous acid ester monosodium salt, monotetradecyl phosphorous acid ester monosodium salt, and monopentadecyl phosphorous acid ester monosodium salt. Potassium salts of the above phosphorous acid esters may also be used.

[0157] Examples of the alkoxysilane having an alkyl group having 6 to 22 carbon atoms include hexyltrimethoxysilane, hexyltriethoxysilane, heptyltrimethoxysilane, heptyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, nonyltrimethoxysilane, nonyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, undecyltrimethoxysilane, undecyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, tridecyltrimethoxysilane, tridecyltriethoxysilane, tetradecyltrimethoxysilane, tetradecyltriethoxysilane, pentadecyltrimethoxysilane, and pentadecyltriethoxysilane.

[0158] Examples of the alkyl thiol having an alkyl group having 6 to 22 carbon atoms include hexyl thiol, heptyl thiol, octyl thiol, nonyl thiol, decyl thiol, undecyl thiol, dodecyl thiol, tridecyl thiol, tetradecyl thiol, pentadecyl thiol, hexadecyl thiol, etc. The alkyl thiol preferably has a thiol group at the end of the alkyl chain.

[0159] Examples of the dialkyl disulfide having an alkyl group having 6 to 22 carbon atoms include dihexyl disulfide, diheptyl disulfide, dioctyl disulfide, dinonyl disulfide, didecyl disulfide, diundecyl disulfide, didodecyl disulfide, ditridecyl disulfide, ditetradecyl disulfide, dipentadecyl disulfide, and dihexadecyl disulfide.

[0160] (Application) The conductive particles can be suitably used for conductive connection of a protective layer-attached electrode comprising an electrode and a protective layer disposed on the surface of the electrode. The conductive particles can be suitably used for conductive connection of a protective layer-attached wiring comprising a wiring and a protective layer disposed on the surface of the wiring. Examples of materials for the electrode and the wiring include precious metals such as gold, silver, and copper. From the viewpoint of further improving the rust resistance of the electrode, it is preferable that the protective layer contains a triazole compound having a mercapto group, a tetrazole compound having a mercapto group, a thiadiazole compound having a mercapto group, a triazole compound having an amino group, or a tetrazole compound having an amino group. When the conductive particles are used for conductive connection of the protective layer-attached electrode or the protective layer-attached wiring, the connection resistance between the electrodes can be more effectively reduced, and the conduction reliability can be more effectively increased.

[0161] The conductive particles can be suitably used for conductive connection of electrodes of flexible members. Examples of connection structures using the flexible members include flexible panels. Flexible panels can be used as curved panels. The conductive particles are preferably used to form connections of flexible panels, and are preferably used to form connections of curved panels.

[0162] (Conductive materials) The conductive material according to the present invention includes the conductive particles and a binder resin. The conductive particles are preferably dispersed in the binder resin and used as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive particles and the conductive material are preferably used for electrical connection between electrodes. The conductive material is preferably a circuit connection material.

[0163] The binder resin is not particularly limited, and may be any known insulating resin.

[0164] Examples of the binder resin include vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers, elastomers, etc. The binder resins may be used alone or in combination of two or more.

[0165] Examples of the vinyl resin include vinyl acetate resin, acrylic resin, and styrene resin. Examples of the thermoplastic resin include polyolefin resin, ethylene-vinyl acetate copolymer, and polyamide resin. Examples of the curable resin include epoxy resin, urethane resin, polyimide resin, and unsaturated polyester resin. The curable resin may be a room temperature curable resin, a thermosetting resin, a photocurable resin, or a moisture curable resin. The curable resin may be used in combination with a curing agent. Examples of the thermoplastic block copolymer include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated product of styrene-butadiene-styrene block copolymer, and hydrogenated product of styrene-isoprene-styrene block copolymer. Examples of the elastomer include styrene-butadiene copolymer rubber, and acrylonitrile-styrene block copolymer rubber.

[0166] The conductive material and the binder resin preferably contain a thermoplastic component or a thermosetting component. The conductive material and the binder resin may contain a thermoplastic component or may contain a thermosetting component. The conductive material and the binder resin preferably contain a thermosetting component. The thermosetting component preferably contains a curable compound that can be cured by heating and a thermosetting agent. The thermosetting agent is preferably a thermal cationic curing initiator. The curable compound that can be cured by heating and the thermosetting agent are used in an appropriate compounding ratio so that the binder resin is cured.

[0167] In addition to the conductive particles and the binder resin, the conductive material may contain various additives such as, for example, a filler, an extender, a softener, a plasticizer, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.

[0168] The method of dispersing the conductive particles in the binder can be a conventionally known dispersion method, and is not particularly limited. The method of dispersing the conductive particles in the binder includes a method of adding the conductive particles to the binder, kneading and dispersing them with a planetary mixer, etc., and a method of uniformly dispersing the conductive particles in water or an organic solvent using a homogenizer, etc., adding them to the binder, and kneading and dispersing them with a planetary mixer, etc. Furthermore, the method of dispersing the conductive particles in the binder includes a method of diluting the binder with water or an organic solvent, etc., adding the conductive particles, and kneading and dispersing them with a planetary mixer, etc.

[0169] The conductive material can be used as a conductive paste, a conductive film, or the like. When the conductive material is a conductive film, a film not containing conductive particles may be laminated on a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.

[0170] In 100% by weight of the conductive material, the content of the binder resin is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, particularly preferably 70% by weight or more, and is preferably 99.99% by weight or less, more preferably 99.9% by weight or less. When the content of the binder resin is equal to or more than the lower limit and equal to or less than the upper limit, the conductive particles are efficiently arranged between the electrodes, and the connection reliability of the connection target members connected by the conductive material can be further increased.

[0171] In 100% by weight of the conductive material, the content of the conductive particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and is preferably 80% by weight or less, more preferably 60% by weight or less, even more preferably 40% by weight or less, particularly preferably 20% by weight or less, and most preferably 10% by weight or less. When the content of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the reliability of conduction between the electrodes can be further improved.

[0172] (Connection structure) A connection structure can be obtained by connecting members to be connected using the conductive particles or the conductive material containing the conductive particles and a binder resin.

[0173] The connection structure includes a first connection target member, a second connection target member, and a connection portion connecting the first and second connection target members. In the connection structure, the material of the connection portion is preferably the conductive particles described above, or a conductive material containing the conductive particles and a binder resin. The connection portion is preferably formed of the conductive particles described above, or a conductive material containing the conductive particles and a binder resin. In the connection structure, the first electrode and the second electrode are electrically connected by the conductive particles. When conductive particles are used as the material of the connection portion, the connection portion itself is a conductive particle. That is, the first and second connection target members are connected by the conductive particles.

[0174] From the viewpoint of more effectively reducing the connection resistance between electrodes, it is preferable that in the connection structure, the standard electrode potential of the main metal in the first conductive portion is smaller than the standard electrode potential of the main metal on the outer surface of the first electrode or the second electrode.

[0175] FIG. 7 is a schematic front cross-sectional view showing a connection structure using conductive particles according to a first embodiment of the present invention.

[0176] A connection structure 51 shown in Fig. 7 includes a first connection target member 52, a second connection target member 53, and a connection portion 54 connecting the first and second connection target members 52, 53. The connection portion 54 is formed by curing a conductive material containing conductive particles 1. Note that, in Fig. 7, the conductive particles 1 are shown in a simplified diagram for convenience of illustration. Instead of the conductive particles 1, conductive particles 11, 21, 31, etc. may be used.

[0177] The first connection target member 52 has a plurality of first electrodes 52a on its surface (upper surface). The second connection target member 53 has a plurality of second electrodes 53a on its surface (lower surface). The first electrodes 52a and the second electrodes 53a are electrically connected by one or more conductive particles 1. Therefore, the first and second connection target members 52 and 53 are electrically connected by the conductive particles 1.

[0178] The method for producing the connection structure is not particularly limited. One example of the method for producing the connection structure is a method in which the conductive material is placed between the first connection target member and the second connection target member to obtain a laminate, and then the laminate is heated and pressurized. The pressure of the pressurization is 9.8×10 4 Pa~4.9×10 6 The heating temperature is about 50° C. to 220° C. The pressure of the pressurization for connecting the electrodes of the flexible printed circuit board, the electrodes arranged on the resin film, and the electrodes of the touch panel is about 9.8×10 4 Pa~1.0×10 6 It is about Pa.

[0179] Specific examples of the connection target members include electronic components such as semiconductor chips, capacitors, and diodes, and circuit boards such as printed circuit boards, flexible printed circuit boards, glass epoxy boards, and glass boards. The connection target members are preferably electronic components. The conductive particles are preferably used for electrically connecting electrodes in electronic components.

[0180] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, silver electrodes, SUS electrodes, molybdenum electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Al and Ga.

[0181] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0182] (Standard electrode potential) Working Example , reference example Regarding the metals used in the first conductive portion, the second conductive portion, the first electrode, and the second electrode used in the comparative example, the standard electrode potentials of the metals are as follows.

[0183] Aluminum: -1.662(V) Iron: -0.440(V) Cobalt: -0.280(V) Nickel: -0.257(V) Tin:-0.138(V) Ruthenium: +0.300(V) Copper:+0.337(V) Rhodium: +0.758(V) Silver:+0.799(V) Palladium: +0.990(V) Platinum:+1.188(V) Gold:+1.830(V)

[0184] ( reference Example 1) (1) Preparation of conductive particles (formation of first conductive portion) Divinylbenzene copolymer resin particles (base particle A, Sekisui Chemical Co., Ltd. "Micropearl SP-203", particle diameter 3 μm) were prepared. 10 parts by weight of the base particle A was dispersed in 100 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution using an ultrasonic disperser, and the solution was filtered to extract the base particle A. Next, the base particle A was added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surface of the base particle A. The base particle A with the activated surface was thoroughly washed with water, and then added to 500 parts by weight of distilled water and dispersed to obtain a suspension.

[0185] In addition, a nickel plating solution (pH 8.5) containing 0.14 mol / L of nickel sulfate, 0.46 mol / L of dimethylamine borane, and 0.2 mol / L of sodium citrate was prepared.

[0186] While stirring the obtained suspension at 60° C., the nickel plating solution was added dropwise to the suspension at a rate of 30 mL / min for 10 minutes, then added dropwise at a rate of 10 mL / min for 40 minutes, and then added dropwise at a rate of 4 mL / min for 80 minutes, thereby performing electroless nickel-boron alloy plating while controlling the content of boron incorporated in the plating film.

[0187] Thereafter, the suspension was filtered to extract the particles, which were then washed with water and dried to obtain particles having a first conductive portion (a conductive layer containing nickel, having a thickness of 0.1 μm) disposed on the surface of the base particle A.

[0188] (2) Preparation of conductive particles (formation of second conductive part) 10 g of the obtained particles were dispersed in 500 mL of ion-exchanged water by an ultrasonic treatment machine to obtain a suspension. A plating solution of pH 10.0 containing 0.02 mol / L of palladium sulfate, 0.04 mol / L of ethylenediamine as a complexing agent, 0.06 mol / L of ammonium formate as a reducing agent, and a crystal regulator was prepared. The obtained plating solution was gradually added while stirring the obtained suspension at 50°C, and electroless palladium plating was performed to form a second conductive part. The electroless palladium plating was terminated when the thickness of the second conductive part reached 20 nm. Conductive particles (particle diameter 3.24 μm) in which a second conductive part (palladium layer, thickness 0.02 μm) was formed on the surface of the first conductive part were obtained.

[0189] (3) Preparation of conductive film (anisotropic conductive film) 30 parts by weight of a phenoxy compound (Inchem's "PKHC"), which is a thermosetting compound, was added to a mixed solvent of 35 parts by weight of PGMEA and 35 parts by weight of methyl ethyl ketone, and stirred at room temperature for 24 hours to obtain a 30% by weight dispersion of the phenoxy compound. Next, a mixture was obtained by mixing 30 parts by weight of the dispersion, 30 parts by weight of an epoxy compound (DIC's "EPICLON HP-4032D"), which is a thermosetting compound, and 30 parts by weight of an imidazole microcapsule hardener (Asahi Kasei's "Novacure HXA3922"), which is a latent type thermosetting agent. 1 part by weight of a silane coupling agent (Shin-Etsu Chemical's "KBM-403") was mixed into the obtained mixture, and the obtained conductive particles were added so that the content in the obtained conductive film was 10% by weight. Then, methyl ethyl ketone was added so that the solid content was 50%, and the mixture was stirred for 5 minutes at 2000 rpm using a planetary stirrer to obtain a mixture. The mixture was applied onto a release-treated polyethylene terephthalate, and the solvent was dried to obtain an anisotropic conductive film with a thickness of 20 μm.

[0190] (4) Fabrication of connection structure A plastic substrate having a copper electrode pattern (first electrode) with an L / S of 10 μm / 10 μm on its upper surface was prepared as the first connection target member, and a flexible substrate having a copper electrode pattern (second electrode) with an L / S of 10 μm / 10 μm on its lower surface was prepared as the second connection target member.

[0191] A conductive film (anisotropic conductive film) immediately after preparation was placed on the upper surface of the plastic substrate to form a conductive film layer (anisotropic conductive film layer). Next, the flexible substrate was laminated on the upper surface of the conductive film layer (anisotropic conductive film layer) so that the electrodes faced each other. Thereafter, a pressure heating head was placed on the upper surface of the flexible substrate while adjusting the temperature of the head so that the temperature of the conductive film layer (anisotropic conductive film layer) was 100°C, and a pressure of 60 MPa was applied to the electrode area to harden the conductive film at 100°C, thereby obtaining a connection structure.

[0192] ( reference Example 2) When forming the first conductive portion, 1 g of nickel particle slurry (average particle diameter 150 nm) was added to the suspension of base particle A. Except for using particles having a core material attached to the surface of base particle A instead of base particle A, reference In the same manner as in Example 1, conductive particles, a conductive film, and a connection structure were obtained.

[0193] ( reference Example 3) Except for using an alumina particle slurry (average particle diameter 150 nm) instead of a nickel particle slurry (average particle diameter 150 nm) when forming the first conductive portion, reference In the same manner as in Example 2, conductive particles, a conductive film, and a connection structure were obtained.

[0194] ( reference Example 4) Except for using a titania particle slurry (average particle diameter 150 nm) instead of a nickel particle slurry (average particle diameter 150 nm) when forming the first conductive portion, reference In the same manner as in Example 2, conductive particles, a conductive film, and a connection structure were obtained.

[0195] ( reference Example 5) When forming the first conductive portion, the particle diameter of the base particle A was changed from 3 μm to 1.5 μm, except for reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0196] ( reference Example 6) When forming the first conductive portion, the particle diameter of the base particle A was changed from 3 μm to 20 μm, except for reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0197] ( reference Example 7) The conductive particles were dispersed in a compound having an alkyl group with 6 carbon atoms to provide an anti-rust treatment to the outer surface of the conductive particles. reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0198] ( reference Example 8) The following monomer composition was placed in a 1000 mL separable flask equipped with a four-neck separable cover, stirring blade, three-way cock, cooling tube and temperature probe, and ion-exchanged water was weighed out so that the solid content of the monomer composition was 5% by weight. The mixture was stirred at 200 rpm and polymerized at 70°C for 24 hours under a nitrogen atmosphere. The monomer composition contained 100 mmol of methyl methacrylate, 1 mmol of N,N,N-trimethyl-N-2-methacryloyloxyethyl ammonium chloride, and 1 mmol of 2,2'-azobis(2-amidinopropane) dihydrochloride. After the reaction was completed, the mixture was freeze-dried to obtain insulating particles having ammonium groups on the surface, an average particle size of 220 nm, and a CV value of 10%.

[0199] The insulating particles were dispersed in ion-exchanged water under ultrasonic irradiation to obtain a 10 wt % aqueous dispersion of the insulating particles.

[0200] reference 10 g of the conductive particles obtained in Example 3 were dispersed in 500 mL of ion-exchanged water, 4 g of the aqueous dispersion of insulating particles was added, and the mixture was stirred at room temperature for 6 hours. After filtering through a 3 μm mesh filter, the mixture was washed with methanol and dried to obtain conductive particles with insulating particles attached thereto (conductive particles with insulating particles).

[0201] Observation with a scanning electron microscope (SEM) revealed that only one coating layer of insulating particles was formed on the surface of the conductive particles. Image analysis was used to calculate the coverage area of ​​the insulating particles (i.e., the projected area of ​​the insulating particle diameter) relative to an area of ​​2.5 μm from the center of the conductive particle, and the coverage rate was 40%.

[0202] When producing a conductive film (anisotropic conductive film), the only difference was that conductive particles with insulating particles were used instead of conductive particles. reference In the same manner as in Example 3, a conductive film and a connection structure were obtained.

[0203] ( reference Example 9) Except for the fact that electroless gold plating was used instead of electroless palladium plating when forming the second conductive portion, reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0204] ( reference Example 10) Except that electroless ruthenium plating was applied instead of electroless palladium plating when forming the second conductive portion, reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0205] ( reference Example 11) As the second connection target member, a flexible substrate having an electrode pattern (second electrode) on the underside in which the main metal of the outer surface of the electrode in the second connection target member is gold was prepared. When producing the connection structure, the same procedure was repeated except that the prepared flexible substrate was used instead of a flexible substrate having a copper electrode pattern (second electrode) with an L / S of 10 μm / 10 μm on the underside. reference A connection structure was obtained in the same manner as in Example 3.

[0206] ( reference Example 12) As the second connection target member, a flexible substrate having an electrode pattern (second electrode) on the underside, in which the main metal of the outer surface of the electrode of the second connection target member is silver, was prepared. When producing the connection structure, the same procedure was repeated except that the prepared flexible substrate was used instead of the flexible substrate having a copper electrode pattern (second electrode) with an L / S of 10 μm / 10 μm on the underside. reference A connection structure was obtained in the same manner as in Example 3.

[0207] ( reference Example 13) As the first connection target member, a plastic substrate having on its upper surface an electrode pattern (first electrode) in which the main metal of the outer surface of the electrode in the first connection target member is gold was prepared. Also, as the second connection target member, a flexible substrate having on its lower surface an electrode pattern (second electrode) in which the main metal of the outer surface of the electrode in the second connection target member is gold was prepared. When producing a connection structure, the same procedure was repeated except that the prepared substrate was used instead of a plastic substrate having on its upper surface a copper electrode pattern (first electrode) with an L / S of 10 μm / 10 μm and a flexible substrate having on its lower surface a copper electrode pattern (second electrode) with an L / S of 10 μm / 10 μm. reference A connection structure was obtained in the same manner as in Example 3.

[0208] ( reference Example 14) 300 g of 0.13 wt % aqueous ammonia solution was placed in a 500 mL reaction vessel equipped with a stirrer and a thermometer. Next, a mixture of 1.9 g of methyltrimethoxysilane, 12.7 g of vinyltrimethoxysilane, and 0.4 g of silicone alkoxy oligomer A ("KR-517" manufactured by Shin-Etsu Chemical Co., Ltd.) was slowly added to the aqueous ammonia solution in the reaction vessel. After the hydrolysis and condensation reactions were allowed to proceed while stirring, 1.6 mL of 25 wt % aqueous ammonia solution was added, and the particles were isolated from the aqueous ammonia solution and the obtained particles were subjected to a 1000 rpm immersion under an oxygen partial pressure of 1000 MPa. -10 The mixture was calcined at 380°C (calcination temperature) for 2 hours (calcination time) at 1000 MPa to obtain organic-inorganic hybrid particles (base particle B). The particle diameter of the obtained organic-inorganic hybrid particles (base particle B) was 3 µm.

[0209] In preparing the conductive particles, except that base particle B was used instead of base particle A, reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0210] Example 15 A nickel plating solution (pH 8.5) containing 0.14 mol / L nickel sulfate, 0.46 mol / L dimethylamine borane, and 0.2 mol / L sodium citrate was prepared as nickel plating solution (1). Also, a nickel plating solution (pH 8.0) containing 0.14 mol / L nickel sulfate and 0.60 mol / L titanium(III) chloride was prepared as nickel plating solution (2).

[0211] When forming the first conductive portion, the nickel plating solution (1) was added dropwise to the suspension at a rate of 6 mL / min for 10 minutes while stirring the resulting suspension at 60°C. Then, the solution was added dropwise at a rate of 2 mL / min for 40 minutes, and then at a rate of 0.8 mL / min for 80 minutes, thereby controlling the content of boron incorporated in the plating film and performing electroless nickel-boron alloy plating on the surface of the base particle A (thickness: 0.02 μm). Next, the liquid temperature was set to 70°C, and the nickel plating solution (2) was gradually added dropwise to perform electroless nickel plating, thereby obtaining a suspension (2).

[0212] Thereafter, the suspension (2) was filtered to extract the particles, which were then washed with water and dried to obtain particles having a first conductive portion (thickness 0.1 μm) made of nickel as the main metal, in which a conductive layer (thickness 0.02 μm) of a nickel-boron alloy and a conductive layer (thickness 0.08 μm) of pure nickel were arranged on the surface of the base particle A. Other than using the obtained particles, reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0213] ( reference Example 16) A plastic substrate and a flexible substrate were prepared in which a protective layer containing 3-mercaptotriazole was formed on the outer surface of the electrode of the first connection target member and the outer surface of the electrode of the second connection target member. When producing a connection structure, the prepared substrate was used instead of a plastic substrate having a copper electrode pattern (first electrode) with an L / S of 10 μm / 10 μm on its upper surface and a flexible substrate having a copper electrode pattern (second electrode) with an L / S of 10 μm / 10 μm on its lower surface. reference A connection structure was obtained in the same manner as in Example 3.

[0214] ( implementation Example 17) As the nickel plating solution, a nickel plating solution (pH 8.5) containing 0.14 mol / L of nickel sulfate, 0.46 mol / L of dimethylamine borane, and 0.2 mol / L of sodium citrate was prepared.

[0215] When forming the first conductive portion, the nickel plating solution was added dropwise to the suspension at a rate of 30 mL / min for 10 minutes while stirring the resulting suspension at 60° C., and then added dropwise for 40 minutes at a rate of 10 mL / min. After that, the nickel plating solution was adjusted to pH 6.8 with sulfuric acid, the reaction temperature was lowered to 30° C. or lower, and the nickel plating solution was added dropwise for 80 minutes at a rate of 4 mL / min to control the amount of boron incorporated in the plating film, thereby performing electroless nickel-boron alloy plating, and a suspension (2) was obtained.

[0216] The suspension (2) was then filtered to extract the particles, which were then washed with water and dried to obtain particles having a first conductive portion (thickness 0.1 μm) with nickel as the main metal formed on the surface of the base particle A. In the first conductive portion of the obtained particles, the average boron content in 100 weight percent of a region (R1) that was 1 / 5 of the thickness from the inner surface of the first conductive portion toward the outside was 1.0 weight percent, and the average boron content in 100 weight percent of a region (R2) that was 1 / 5 of the thickness from the outer surface of the first conductive portion toward the inside was 6.0 weight percent. Apart from using the obtained particles, reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0217] Comparative Example 1 A nickel plating solution (pH 8.0) containing 0.14 mol / L nickel sulfate, 0.46 mol / L dimethylamine borane, and 0.4 mol / L sodium citrate was prepared as nickel plating solution (1). Also, a nickel plating solution (pH 6.0) containing 0.05 mol / L nickel sulfate, 0.95 mol / L dimethylamine borane, and 0.8 mol / L sodium citrate was prepared as nickel plating solution (2).

[0218] When forming the first conductive portion, the nickel plating solution (1) was added dropwise to the suspension at a dropping rate of 5 mL / min for 40 minutes while stirring the resulting suspension at 60° C. Thereafter, the liquid temperature was set to 20° C., and the nickel plating solution (2) (pH 6.0) was gradually added dropwise to perform electroless nickel-boron alloy plating, thereby obtaining a suspension (2).

[0219] The suspension (2) was then filtered to extract the particles, which were then washed with water and dried to obtain particles having a first conductive portion (a conductive layer containing nickel, 0.1 μm thick) disposed on the surface of the base particle A. In the first conductive portion of the obtained particles, the average boron content in 100 weight percent of a region that is 1 / 5 of the thickness from the inner surface of the first conductive portion toward the outside was 0.05 weight percent, and the average boron content in 100 weight percent of a region that is 1 / 5 of the thickness from the outer surface of the first conductive portion toward the inside was 15.0 weight percent. Apart from using the obtained particles, reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0220] Comparative Example 2 As the nickel plating solution, a nickel plating solution (pH 9.0) containing 0.25 mol / L of nickel sulfate, 0.25 mol / L of sodium hypophosphite, and 0.15 mol / L of sodium citrate was prepared.

[0221] When forming the first conductive portion, the above nickel plating solution was gradually dropped into the suspension while stirring the obtained suspension at 60°C, and electroless nickel-phosphorus alloy plating was performed. Thereafter, the suspension was filtered to extract the particles, which were washed with water and dried to obtain particles having a nickel-phosphorus layer (thickness 0.1 μm) disposed on the surface of the base particle A. The nickel content in 100% by weight of the conductive layer was 97.0% by weight, and the phosphorus content was 3.0% by weight. Apart from using the obtained particles, reference In the same manner as in Example 3, conductive particles, a conductive material, and a connection structure were obtained.

[0222] Comparative Example 3 As the nickel plating solution, a nickel plating solution (pH 10.0) containing 0.40 mol / L of nickel sulfate, 0.15 mol / L of sodium hypophosphite, and 0.15 mol / L of sodium citrate was prepared.

[0223] When forming the first conductive portion, the nickel plating solution was gradually dropped into the obtained suspension while stirring the suspension at 80°C, and electroless nickel-phosphorus alloy plating was performed. The suspension was then filtered to extract the particles, which were then washed with water and dried to obtain particles having a nickel-phosphorus layer (thickness 0.1 μm) disposed on the surface of the base particle A. The nickel content in 100% by weight of the conductive layer was 99.5% by weight, and the phosphorus content was 0.5% by weight. Apart from using the obtained particles, reference In the same manner as in Example 3, conductive particles, a conductive material, and a connection structure were obtained.

[0224] Comparative Example 4 As the first connection target member, a plastic substrate having an electrode pattern (first electrode) on the upper surface, in which the main metal of the outer surface of the electrode in the first connection target member is gold, was prepared. Also, as the second connection target member, a flexible substrate having an electrode pattern (second electrode) on the lower surface, in which the main metal of the outer surface of the electrode in the second connection target member is gold, was prepared. When producing the connection structure, the connection structure was obtained in the same manner as in Comparative Example 3, except that the prepared substrate was used instead of the plastic substrate having a copper electrode pattern (first electrode) with L / S of 10 μm / 10 μm on the upper surface and the flexible substrate having a copper electrode pattern (second electrode) with L / S of 10 μm / 10 μm on the lower surface.

[0225] Comparative Example 5 Except that the second conductive portion was not formed when the conductive particles were prepared, reference In the same manner as in Example 16, conductive particles, a conductive material, and a connection structure were obtained.

[0226] Comparative Example 6 Except for the fact that electroless cobalt plating was performed when forming the second conductive portion, reference In the same manner as in Example 3, conductive particles, a conductive film, and a connection structure were obtained.

[0227] (Particle diameter of conductive particles) The particle size of the conductive particles was measured using a laser diffraction particle size distribution measuring device ("LA-920" manufactured by Horiba, Ltd.).

[0228] (evaluation) (1) Average content of nickel and boron in 100% by weight of the first conductive portion During the preparation of the conductive particles, only the first conductive portion was formed to prepare particles on which only the first conductive portion was formed. 5 g of the prepared particles was added to a mixture of 5 mL of 60% nitric acid and 10 mL of 37% hydrochloric acid, and the first conductive portion was completely dissolved to obtain a solution. The nickel and boron contents of the obtained solution were analyzed by a high-frequency inductively coupled plasma ion source mass spectrometer ("ICP-MS" manufactured by Hitachi High-Tech Science Corporation). Note that, if it is difficult to prepare 5 g of the above particles, the particles used for the measurement may be less than 5 g.

[0229] (2) Average nickel and boron content in the thickness direction of the first conductive portion The distribution of the nickel and boron contents in the thickness direction of the first conductive portion was measured.

[0230] Using a focused ion beam, a thin-film slice of the obtained conductive particle was prepared. Using a field emission transmission electron microscope (JEM-2010FEF manufactured by JEOL Ltd.), the nickel and boron contents in the thickness direction of the first conductive part were measured by an energy dispersive X-ray analyzer (EDS). From these results, the average contents of nickel (Ni) and boron (B) in 100% by weight of the region (R1) (region with 20% thickness on the inner surface side) from the inner surface of the first conductive part to 1 / 5 of the thickness toward the outside, and the region (R2) (region with 20% thickness on the outer surface side) from the outer surface of the first conductive part to 1 / 5 of the thickness toward the inside were obtained. From the obtained results, the absolute value of the difference between the average boron content in 100% by weight of the region (R1) and the average boron content in 100% by weight of the region (R2) (absolute value of the difference in the average boron content) was calculated.

[0231] (3) Connection resistance A (initial) The connection resistance A between the opposing electrodes of the obtained connection structure was measured by a four-terminal method. Note that, based on the relationship of voltage = current x resistance, the connection resistance can be obtained by measuring the voltage when a constant current is passed. The connection resistance A was also evaluated according to the following criteria.

[0232] [Evaluation criteria for connection resistance A] ○○○: Connection resistance A is 2.0Ω or less ○○: Connection resistance A is greater than 2.0 Ω and less than 3.0 Ω ○: Connection resistance A is more than 3.0Ω and 5.0Ω or less △: Connection resistance A is over 5.0Ω and 10Ω or less ×: Connection resistance A exceeds 10 Ω

[0233] (4) Connection resistance B (after reliability test) The connection structures obtained in the above (1) evaluation of initial connection resistance were left at 85°C and 85% relative humidity. 1000 hours after the start of leaving them, the connection resistance B between the electrodes was measured by the four-terminal method in the same manner as in the above (3) evaluation of connection resistance A. In addition, the connection resistance B was evaluated according to the following criteria.

[0234] [Connection resistance B criteria] ○○○: Connection resistance B is less than 1.25 times the connection resistance A ○○: Connection resistance B is 1.25 times or more but less than 1.5 times the connection resistance A. ○: Connection resistance B is 1.5 times or more but less than 2 times the connection resistance A. △: Connection resistance B is more than twice but less than three times the connection resistance A. ×: Connection resistance B is more than three times that of connection resistance A

[0235] (5) Cracks in conductive parts (initial stage) 1 g of the obtained conductive particles, 20 g of toluene, and 45 g of zirconia balls with a diameter of 0.5 mm were mixed and stirred for 2 minutes at 400 rpm with a stirring blade with a diameter of 3 cm. The solid-liquid separated particles were dried and then observed with an SEM. The number of conductive particles with cracks in the conductive part out of 1000 conductive particles was counted, and the cracks in the conductive part were evaluated according to the following criteria. The amount of the conductive particles used to evaluate the cracks in the conductive part may be less than 1 g as long as 1000 particles can be observed.

[0236] [Criteria for determining cracks in conductive parts (initial stage)] ○○○: The percentage of conductive particles with cracks in the conductive part is less than 3% ○○: The percentage of conductive particles with cracks in the conductive part is 3% or more but less than 10% ○: The percentage of conductive particles with cracks in the conductive portion is 10% or more and less than 20%. △: The percentage of conductive particles with cracks in the conductive portion is 20% or more but less than 30%. ×: The percentage of conductive particles with cracks in the conductive portion is 30% or more.

[0237] (6) Cracks in conductive parts (after reliability testing) The obtained conductive particles were left at 85°C and 85% relative humidity. After 1000 hours from the start of leaving, 1 g of the left conductive particles, 20 g of toluene, and 45 g of zirconia balls with a diameter of 0.5 mm were mixed and stirred for 2 minutes at 400 rpm with a stirring blade with a diameter of 3 cm. The solid-liquid separated particles were dried and then observed with an SEM. The number of conductive particles with cracks in the conductive part out of 1000 conductive particles was counted, and the cracks in the conductive part were evaluated according to the following criteria. The amount of the conductive particles used to evaluate the cracks in the conductive part may be less than 1 g as long as 1000 particles can be observed.

[0238] [Criteria for determining cracks in conductive parts (after reliability testing)] ○○○: The percentage of conductive particles with cracks in the conductive part is less than 5% ○○: The percentage of conductive particles with cracks in the conductive part is 5% or more but less than 15% ○: The percentage of conductive particles with cracks in the conductive portion is 15% or more and less than 25%. △: The percentage of conductive particles with cracks in the conductive portion is 25% or more but less than 35%. ×: The percentage of conductive particles with cracks in the conductive portion is 35% or more.

[0239] The details of the conductive particles and the results are shown in Tables 1 to 4 below.

[0240] [Table 1]

[0241] [Table 2]

[0242] [Table 3]

[0243] [Table 4] [Explanation of symbols]

[0244] 1, 11, 21, 31...Conductive particles 2...Base material particles 3, 13, 23, 33...First conductive part 4, 24, 34...Second conductive part 13A, 13B…Conductive part 25…core substance 26...Insulating materials 21A, 23A, 24A…Protrusion 31A, 33A, 34A…Protrusion 51...Connection structure 52...First connection target member 52a...first electrode 53...Second connecting member 53a...second electrode 54…Connection

Claims

1. A base particle; A first conductive portion disposed on a surface of the base particle; a second conductive portion disposed on a surface of the first conductive portion; the first conductive portion contains nickel and boron and does not contain phosphorus; an absolute value of a difference between an average boron content in 100 weight % of a region having a thickness of 1 / 5 from the inner surface of the first conductive portion toward the outside and an average boron content in 100 weight % of a region having a thickness of 1 / 5 from the outer surface of the first conductive portion toward the inside is 1.0 weight % or more and 5 weight % or less; Conductive particles, wherein a standard electrode potential of a base metal in the first conductive portion is smaller than a standard electrode potential of a base metal in the second conductive portion.

2. 2 . The conductive particle according to claim 1 , wherein an absolute value of a difference between a standard electrode potential of the main metal in the first conductive portion and a standard electrode potential of the main metal in the second conductive portion is 0.05 V or more and 3 V or less.

3. an average content of boron in 100% by weight of a region of ⅕ of the thickness from the inner surface of the first conductive portion toward the outside is 0% by weight or more and 10% by weight or less; The conductive particle according to claim 1 or 2, wherein the average boron content in 100% by weight of a region 1 / 5 of the thickness from the outer surface of the first conductive portion toward the inside is 0% by weight or more and 10% by weight or less.

4. The conductive particle according to any one of claims 1 to 3, wherein the average content of nickel in the first conductive portion (100% by weight) is 50% by weight or more and 99.9% by weight or less.

5. The conductive particle according to any one of claims 1 to 4, wherein the average content of boron in the first conductive portion (100% by weight) is 0.001% by weight or more and 10% by weight or less.

6. The conductive particle according to any one of claims 1 to 5, wherein the main metal in the second conductive portion is tin, copper, palladium, ruthenium, platinum, silver, rhodium, iridium or gold.

7. The conductive particle according to any one of claims 1 to 6, wherein an outer surface of the second conductive portion is subjected to an anti-rust treatment.

8. 8. The conductive particle according to claim 7, wherein an outer surface of the second conductive portion is subjected to an anti-rust treatment with a compound having an alkyl group having 6 to 22 carbon atoms.

9. The conductive particle according to any one of claims 1 to 8, wherein the particle diameter of the base particle is 0.1 µm or more and 100 µm or less.

10. The conductive particle according to any one of claims 1 to 9, having a plurality of protrusions on an outer surface of the first conductive portion or the second conductive portion.

11. The conductive particle according to claim 10, comprising a plurality of core materials that raise the surface of the first conductive portion or the second conductive portion to form a plurality of the protrusions inside or on the inside of the first conductive portion or the second conductive portion.

12. The conductive particle described in claim 10, which does not have a plurality of core materials inside or on the inside of the first conductive portion or the second conductive portion that raise the surface of the first conductive portion or the second conductive portion to form a plurality of the protrusions.

13. The conductive particle according to any one of claims 1 to 12, comprising an insulating material disposed on an outer surface of the second conductive portion.

14. The conductive particles according to any one of claims 1 to 13, which are used for conductive connection of a protective layer-attached electrode comprising an electrode and a protective layer disposed on a surface of the electrode.

15. The conductive particle according to any one of claims 1 to 13, which is used for conductive connection of electrodes of flexible members.

16. A conductive material comprising the conductive particles according to any one of claims 1 to 13 and a binder resin.

17. a first connection target member having a first electrode on a surface thereof; a second connection target member having a second electrode on a surface thereof; a connection portion that connects the first connection target member and the second connection target member, the connection portion is formed of the conductive particles according to any one of claims 1 to 13, or is formed of a conductive material containing the conductive particles and a binder resin; A connection structure, wherein the first electrode and the second electrode are electrically connected by the conductive particles.

18. The connection structure according to claim 17 , wherein a standard electrode potential of a base metal in the first conductive portion is lower than a standard electrode potential of a base metal on an outer surface of the first electrode or the second electrode.

Citation Information

Patent Citations

  • Conductive particle

    JP2013020721A

  • Conductive particle, conductive material and connection structure

    JP2014241280A

  • Conductive particle, conductive material, and connection structure

    JP2016006764A

  • Photosensitive resin composition and photosensitive element

    JP2017009702A